Solid-state energy harvesters based on transition metal suboxides

By using transition metal low oxides and multi-layer structure solid electrolytes in solid-state energy harvesters and combining carbon materials, the problems of energy collection and storage in solid-state environments are solved, and efficient energy collection and stable performance are achieved.

CN112805839BActive Publication Date: 2024-12-27OMEGA ENERGY SYST INC
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN201980018924.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-03-12
Filing Date
2019-03-11
Publication Date
2024-12-27
Estimated Expiration
2039-03-11

AI Technical Summary

Technical Problem

Existing energy harvesters are unable to effectively collect and store energy in a solid-state environment, and lack the technology to use devices that use solid-state electrolytes to generate energy on demand from the surrounding environment.

Method used

Using solid-state energy collectors, using a variety of oxides of transition metals, especially low oxides containing tungsten, titanium and cobalt, the polarity is changed through the presence of gaseous oxygen and water vapor, and the transfer of electrons and energy collection is realized. A combination of solid electrolyte and adhesive including a multi-layer structure is used to improve performance using carbon materials.

Benefits of technology

The ability to continuously collect energy in a solid-state environment is realized, the power density and stability of the energy collector is improved, and it can spontaneously recharge in different gas environments, extending the service life of the equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112805839B_ABST
    Figure CN112805839B_ABST
Patent Text Reader

Abstract

Solid-state energy harvesters and methods of making and using solid-state energy harvesters are provided, the solid-state energy harvesters including layers of metal suboxides and ceria that utilize a solid-state electrolyte to generate power. The solid-state energy harvesters can have two or three electrodes per cell and generate power in the presence of water vapor and oxygen.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] All references cited herein, including but not limited to patents and patent applications, are incorporated by reference in their entirety.

[0002] CROSS-REFERENCE TO RELATED APPLICATIONS

[0003] This application claims the benefit of U.S. Provisional Patent Application No. 62 / 641,779, filed on March 12, 2018, which is hereby incorporated by reference in its entirety.

[0004] background

[0005] An energy harvester is a device that does not store energy, but rather collects energy from the environment. See, for example, U.S. Patents Nos. 8,115,683; 10,147,863; 10,142,125 and 10,141,492. For example, energy harvesters collect energy from a variety of sources (e.g., solar, thermal, wind, salinity gradients, kinetic, piezoelectric, pyroelectric, thermoelectric, and RF-harvesting devices such as crystal radios). Some are very high energy generators, such as wind and solar, and some are very low energy outputs, such as piezoelectric or RF harvesters. However, these energy harvesters do not store energy, but rather collect energy from their surroundings.

[0006] There have been recent efforts to create a battery that uses only electrons rather than ions to transfer charge. Sigler, D., “All-Electron Battery–Stanford Strikes Again,” CAFE Foundation (3 / 28 / 2015) (cafe.foundation / blog / electron-battery-stanford-strikes). However, these devices store rather than harvest energy.

[0007] What is needed is an energy harvester device that uses solid-state electrolytes to generate on-demand energy from the surrounding environment for a variety of applications.

[0008] Overview

[0009] Aspects described herein provide solid-state energy harvesters, solid-state energy harvester systems, and related methods, in certain aspects, solid-state energy harvesters, solid-state energy harvester systems, and related methods use multiple oxides of transition metals that allow non-integer valence states in the mass of their crystal structures. Aspects described herein do not use liquid electrolytes, but use electrons to transfer charge.

[0010] Exemplary oxides used in the described aspects change their polarity depending on the presence of gaseous oxygen and gaseous water vapor in the environment. In one aspect, the power generated by the energy harvester is continuous as long as the two components (e.g., gaseous oxygen and gaseous water vapor) are present. Without being bound by theory, it is believed that water vapor plays an important role, including the self-ionization of the molecule into hydroxyl ions and protons. This can expand the exchange potential of the cerium suboxide, allowing subsequent redox reactions.

[0011] The aspects described herein may also be used as batteries or capacitors.

[0012] In certain aspects, the transition metal oxides as described herein can be "suboxides" of tungsten, titanium, and cobalt. Each has an average valence less than the stable integer value of the oxide of the element, and is therefore referred to as a "suboxide". In this aspect, the chemical value is the average of the crystal mass. This imbalance provides each compound with a different electronegativity for each compound. The active cathode material Co3O4 is less electronegative than the anode material Ti4O7, and is therefore "electropositive" relative to the anode. In one aspect, the solid state electrolyte (SSE) includes CeO2, and the tungsten suboxide WO 2.9 Transfer charge.

[0013] Without being bound by theory, it is believed that oxygen enters the cathode, carrying its two negative charges (electrons), and becomes embedded in the crystal structure. Defects in the Co3O4 create excess electrons that slide onto the CeO2 crystals with their loosely bound oxygen atoms, which carry two electrons. These electrons are due to the WO 2.9 The lower electronegativity of the anode is attracted and facilitated by the CeO2 "electrolyte," migrating freely throughout the cell. The Ti4O7 in the anode collects the excess electrons, which can then be released to an external circuit to generate energy.

[0014] Aspects described herein provide a solid-state energy harvester comprising a solid-state electrolyte (SSE) comprising a mixture of a first transition metal suboxide and a lanthanide oxide or lanthanide dioxide; a first layer comprising a second transition metal suboxide and the SSE; and a second layer comprising a third transition metal suboxide and the SSE, wherein the second transition metal suboxide and the third transition metal suboxide are different from each other.

[0015] In one aspect, a solid-state energy harvester is provided, the solid energy harvester having a first layer comprising a first transition metal suboxide, a second layer comprising a second transition metal suboxide, and a third layer comprising a third transition metal suboxide. In this aspect, the second layer is disposed between the first layer and the third layer, and the first transition metal oxide, the second transition metal oxide, and the third transition metal oxide are different from each other. In another aspect, the first layer acts as an anode and the second layer acts as a cathode, wherein there is no intermediate layer of a solid-state electrolyte. In another aspect, all layers each further comprise cerium dioxide. In yet another aspect, all layers each further comprise tungsten suboxide. In another aspect, all layers each further comprise a binder. The binder can be, for example, a polymer binder, such as poly(vinyl alcohol) (PVA), carboxymethyl cellulose (CMC), or polytetrafluoroethylene (PTFE). In another aspect, the binder is unsintered PTFE.

[0016] In another aspect, the anode electrode and cathode electrode also comprise carbon. In this aspect, both carbon black and powdered graphite can improve performance (e.g., power density). In another aspect, the SSE remains unchanged. In this aspect, the separation of charge spans the high resistance of the SSE layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 An exemplary crystal structure of ceria is shown;

[0019] Figure 2 An exemplary cerium reduction mechanism is shown;

[0020] Figure 3 Diagram showing how oxygen dissolves in water;

[0021] Figure 4 Figure 2 shows the effect of dehydration on tungsten suboxide WO 2.9 The influence of crystal structure;

[0022] Figure 5 An exemplary crystal structure of a cobalt suboxide, also known as cobalt (II, III) oxide (Co3O4), is shown;

[0023] Figure 6 An exemplary crystal structure of Ti4O7 is shown;

[0024] Fig. 7A An exemplary physical layout of one aspect of a solid-state energy harvester having multiple layers of expanded metal between electrodes is shown;

[0025] Figure 7B An exemplary physical layout of a six-electrode energy harvester is shown;

[0026] Figure 8 The figure shows the use of a roller mill to manufacture a rolled electrode;

[0027] Fig. 9 is a graph showing exemplary current density during a short circuit of an energy harvester;

[0028] Fig.10 is a graph showing an exemplary recovery of an energy harvester after a short circuit;

[0029] Fig.11 is a graph showing exemplary results for a non-discharging energy harvester in oxygen, argon (0% oxygen), and air after short circuiting, with the open circuit voltage (OCV) recorded;

[0030] Fig.12 is a graph showing exemplary short circuit current density in air, oxygen, and argon (0% oxygen);

[0031] Fig.13 is a graph showing an exemplary voltammogram of a dead-shorted energy harvester after standing in air for 48 hours;

[0032] Fig.14 is a graph showing the AC impedance of an exemplary solid-state energy harvester;

[0033] Fig.15 is a diagram showing a Nyquist plot of an exemplary solid-state energy harvester;

[0034] Fig.16 An exemplary solid-state energy harvester is shown with nickel expanded metal between all electrodes;

[0035] Fig.17 is a graph showing a voltammogram of an exemplary solid-state energy harvester;

[0036] Fig.18A and Fig.18B is a graph showing short circuit discharge and open circuit voltage ("OCV") spontaneous recharging of an exemplary solid-state energy harvester;

[0037] Fig.19 is a diagram of an exemplary 3-layer thin film solid-state energy harvester;

[0038] Fig. 20 is a voltammogram of an exemplary solid-state energy harvester;

[0039] Fig.21is a graph showing long Open Circuit Voltage (OCV) of an exemplary solid-state energy harvester;

[0040] Fig. 22 is a cross section of an exemplary solid-state energy harvester;

[0041] Fig.23 is a graph showing current density for three 24 hour tests of an exemplary solid-state energy harvester;

[0042] Fig.24 is a graph showing OCV recovery of an exemplary solid-state energy harvester after three tests in different ambient gases including air, oxygen, and inert gas argon (0% oxygen);

[0043] Fig.25 is a graph showing the OCV between tests, showing the OCV recovery rate in three different gas environments (oxygen, air, and (0% oxygen));

[0044] Fig.26 is a graph showing a dead-short discharge over the life of an exemplary solid-state energy harvester;

[0045] Fig. 27 is a graph showing long term discharge of an exemplary solid-state energy harvester over eight days;

[0046] Fig.28 is a graph showing the effect of adding oxygen or argon (0% oxygen) or air (20% oxygen) to a test chamber during energy harvester discharge of an exemplary solid-state energy harvester;

[0047] Fig.29 is a graph showing impedance as a function of current density when an exemplary solid-state energy harvester is humidified to water saturation conditions;

[0048] Fig.30 shows the limiting currents obtained from voltammograms for three exemplary energy harvester designs;

[0049] Fig.31 shows the general electron flow of an exemplary energy harvester;

[0050] Fig.32 An exemplary three-layer cell design with an anode (A), separator (Sep), and cathode (C) is shown;

[0051] Fig.33shows the power density curves with graphite added to the anode and cathode in a three-layer cell design compared to a two-electrode design without graphite added to the anode and cathode, and after a short circuit lasting 24 hours followed by open circuit voltage (OCV) recovery;

[0052] Fig.34 It is shown that the power density during a dead short circuit discharge is increased by about 10 times in a three-layer design with carbon added to the electrodes compared to a two-electrode design without carbon added to the electrodes;

[0053] Fig.35 shows a 100 mV discharge in air, oxygen, and argon over a 24 hour period in a three-layer design with carbon added to the electrodes; and

[0054] Fig.36 Power curves for three exemplary designs are shown as labeled: a two-electrode design with no carbon, a three-electrode design with 3% nanographite added to the anode and cathode and an SSE layer between the anode and cathode, and a three-electrode design with 3% Vulcan 72 carbon black added to the anode and cathode and an SSE layer between the anode and cathode.

[0055] Detailed Description

[0056] The disclosed methods, compositions and devices may be described both generally and specifically below. It should be noted that when a description is specific to an aspect, that aspect should not limit the scope of the device or method in any way. The features and properties of the present disclosure will become more apparent from the detailed description set forth below when taken in conjunction with the accompanying drawings.

[0057] Aspects disclosed herein provide a solid-state energy harvester, comprising: a solid electrolyte (SSE) comprising a mixture of a first transition metal suboxide and a lanthanide oxide or lanthanide dioxide; a first layer comprising a second transition metal suboxide and the SSE; and a second layer comprising a third transition metal suboxide and the SSE. In this aspect, the second transition metal suboxide and the third transition metal suboxide are different from each other.

[0058] Aspects disclosed herein provide a solid-state energy harvester having: a first layer comprising a first transition metal suboxide and a solid state electrolyte (SSE); a second layer comprising a mixture of a second transition metal suboxide and a lanthanide oxide or a lanthanide dioxide, wherein the mixture forms the SSE; and a third layer comprising a third transition metal suboxide and the SSE; wherein the first transition metal suboxide and the third transition metal suboxide are different from each other.

[0059] The term "suboxide" indicates that for the element, the average valence is less than a stable integer value. This value is, for example, an average value for a crystalline substance. This imbalance in valence provides a different electronegativity for each compound. For example, a cathode material (e.g., Co3O4) is less electronegative than an anode material (e.g., Ti4O7), and is therefore "electropositive" relative to the anode.

[0060] The term "transition metal" refers to an element whose atoms have a partially filled d sub-shell, or which can produce cations with incomplete d sub-shells. IUPAC, Compendium of Chemical Terminology, 2nd Edition (the "Gold Book") (1997), (2006-); Groups 3 to 12 on the periodic table. "Transition metal suboxide" refers to a suboxide of a transition metal. The term "suboxide" refers to an oxide containing a lower amount of oxygen than an oxide. For example, a suboxide has an average valence less than the stable integer value of the oxide of the element, where the value is the average value of the crystalline substance.

[0061] In one aspect, the first transition metal suboxide is selected from the group consisting of tungsten suboxide, cobalt suboxide, Co3O4, Na 1.0 Mo 1.5 WO 6.0 、Na 0.9 Mo6O 17 、Na 1.0 Ti 1.5 WO 4.5 、Na 1.2 Ti 0.34 WO4, Ti4O7, Ti5O9, K 1.28 Ti8O 16 , K 1.04 Ti8O 16 , K 0.48 Ti8O 16 、Na4WO3、Na 0.90 WO 1.81 、Na 0.82 WO 1.81 、Na 0.74 WO 1.81 , K 0.9 WO3、WO 2.72 , WO 2.82 , WO 2.9 、Na2WO4、Na 8.2 WO, Na2O2WO3, Na 1.2 Ti 0.34 WO4、Na1.2 Cu 0.31 WO 7.2 、Na 1.2 Mo 0.31 WO 5.2 and Na2O4WO3.

[0062] In another aspect, the second transition metal suboxide is selected from the group consisting of tungsten suboxide, cobalt suboxide, Co3O4, Na 1.0 Mo 1.5 WO 6.0 、Na 0.9 Mo6O 17 、Na 1.0 Ti 1.5 WO 4.5 、Na 1.2 Ti 0.34 WO4, Ti4O7, Ti5O9, K 1.28 Ti8O 16 , K 1.04 Ti8O 16 , K 0.48 Ti8O 16 、Na4WO3、Na 0.90 WO 1.81 、Na 0.82 WO 1.81 、Na 0.74 WO 1.81 , K 0.9 WO3、WO 2.72 , WO 2.82 , WO 2.9 、Na2WO4、Na 8.2 WO, Na2O2WO3, Na 1.2 Ti 0.34 WO4、Na 1.2 Cu 0.31 WO 7.2 、Na 1.2 Mo 0.31 WO 5.2 and Na2O4WO3.

[0063] In a further aspect, the third transition metal suboxide is selected from the group consisting of tungsten suboxide, cobalt suboxide, Co3O4, Na 1.0 Mo 1.5 WO 6.0 、Na 0.9 Mo6O 17 、Na 1.0 Ti 1.5 WO 4.5 、Na 1.2 Ti 0.34WO4, Ti4O7, Ti5O9, K 1.28 Ti8O 16 , K 1.04 Ti8O 16 , K 0.48 Ti8O 16 、Na4WO3、Na 0.90 WO 1.81 、Na 0.82 WO 1.81 、Na 0.74 WO 1.81 , K 0.9 WO3、WO 2.72 , WO 2.82 , WO 2.9 、Na2WO4、Na 8.2 WO, Na2O2WO3, Na 1.2 Ti 0.34 WO4、Na 1.2 Cu 0.31 WO 7.2 、Na 1.2 Mo 0.31 WO 5.2 and Na2O4WO3.

[0064] In yet another aspect, the transition metal suboxide (ie, the first transition metal suboxide, the second transition metal suboxide, or the third transition metal suboxide) is selected from the group consisting of boron, iron, copper, and nickel.

[0065] In another aspect, the first transition metal suboxide is an alkali metal suboxide. The term "alkali metal" refers to a metal from Group 1 of the IUPAC (International Union of Pure and Applied Chemistry) Periodic Table of Elements (e.g., lithium (Li), sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), and francium (Fr)). In one aspect, the alkali metal suboxide is selected from the group consisting of rubidium and cesium.

[0066] In another aspect, the lanthanide oxide is selected from the group consisting of ceria, lanthanum oxide or dioxide, praseodymium oxide or dioxide, neodymium oxide or dioxide, promethium oxide or dioxide, samarium oxide or dioxide, europium oxide or dioxide, gadolinium oxide or dioxide, terbium oxide or dioxide, dysprosium oxide or dioxide, holmium oxide or dioxide, erbium oxide or dioxide, thulium oxide or dioxide, ytterbium oxide or dioxide, and lutetium oxide or dioxide.

[0067] In another aspect, the first transition metal suboxide is Ti4O7. In yet another aspect, the second transition metal suboxide is WO2.9 In another aspect, the third transition metal suboxide is Co3O4.

[0068] In another aspect, the first layer and the second layer substantially comprise a noble metal. The term "noble metal" refers to a metallic element that is resistant to corrosion and oxidation (e.g., ruthenium (Ru), rhodium (Rh), palladium (Pd), silver (Ag), osmium (Os), iridium (Ir), platinum (Pt), gold (Au), mercury (Hg), [2] [3] [4] rhenium (Re) [5] and copper (Cu)). In yet another aspect, the first layer and the second layer comprise a noble metal.

[0069] The solid collector having the first layer, the second layer and the third layer may each further include a binder (e.g., unsintered Teflon (PTFE), FEP, paraffin wax and epoxy resin). The term "binder" refers to molecules that hold the particles of the active ingredient together (e.g., like bugs in a spider's web).

[0070] In a further aspect, the anode and cathode further comprise carbon (e.g., carbon black such as CABOT Vulcan XC72R (also referred to as "V72") or powdered graphite such as Asbury Graphite Mills "Nano307" powder). In this aspect, the cathode and / or anode may be loaded with about from 0.5% to about 5% carbon. In another aspect, the SSE separator layer does not comprise carbon, thereby enhancing the separation of charge across its higher impedance compared to the anode and cathode.

[0071] Additional aspects provide a solid-state energy harvester wherein the first layer is an anode and the third layer is a cathode. In this aspect, the second layer can be a SSE separator. In this aspect, the anode can contain between about 0.01% and about 14% water. The cathode can contain between about 0.01% and about 4% water. In another aspect, the anode contains about 7% water and the cathode contains about 2% water. In yet another aspect, the SSE contains about 2% water.

[0072] The term "anode" refers to the electrode that releases electrons and becomes the negative terminal of the energy harvester. The term "cathode" refers to the electrode that consumes electrons and becomes the positive electrode of the energy harvester. The term "charge" refers to the movement of electrons as ions, free radicals, or electrons to make the energy harvester an active "charged" state.

[0073] In yet another aspect, the first transition metal suboxide, the second transition metal suboxide, and the third transition metal suboxide each have a stoichiometry M x-y ,in:

[0074] M is a transition metal,

[0075] x is the base valence value of the transition metal M,

[0076] y is the deviation from unity, and

[0077] When M is titanium, x is 4 and y is at least 0.5,

[0078] When M is cobalt, x is 3 and y is at least 0.3, and

[0079] When M is tungsten, x is 5 and y is at least 0.2.

[0080] In another aspect, the first layer of the solid-state energy harvester is electrically connected to a first current collector, and the second layer is electrically connected to a second current collector. The term "current collector" refers to a conductive material that collects electrons from a reactive layer to transfer them to another layer or an external circuit. The first current collector and the second current collector may include a metal selected from the group consisting of gold, nickel, copper, brass, bronze, and carbon.

[0081] The first current collector and the second current collector may include a porous material. In another aspect, the porous material includes greater than about 50% pores. The pores may have a diameter from about 10 μm to about 40 μm.

[0082] In yet another aspect, the first current collector and the second current collector each include foamed metal. The foamed metal may be a porous material (eg, a material with greater than 50% pores), and the pores may have a diameter of from about 10 μm to about 40 μm.

[0083] The first current collector and the second current collector may each include perforated metal. The term "perforated metal" refers to a conductive layer that contains many small perforations to make the layer porous, but still highly conductive to electrons. If the active material is compressed into the holes, electrons or ions also pass freely through the layer.

[0084] In further aspects, the first and second current collectors can each include a porous conductive material (eg, carbon). The carbon porous material can be greater than about 50% pores, and the pores can have a diameter from about 10 μm to about 40 μm.

[0085] A further aspect provides a solid-state energy harvester system having a first energy harvester and a second energy harvester as described herein. In this aspect, the first layer of the first energy harvester is electrically connected to the third layer of the second energy harvester. In this aspect, the first layer of each of the first energy harvester and the second energy harvester may include a titanium suboxide, and the third layer of each of the first energy harvester and the second energy harvester may include a cobalt suboxide, wherein the second layer includes cerium dioxide and tungsten suboxide.

[0086] In another aspect, the first layer of the first energy harvester and the third layer of the second energy harvester can each be operably attached to a current collector.

[0087] Another aspect provides a solid-state energy harvester having a first layer, a second layer, and a third layer, the first layer comprising a first transition metal suboxide, a tungsten suboxide, and ceria, the second layer comprising ceria and tungsten suboxide, and the third layer comprising a second transition metal suboxide, tungsten suboxide, and ceria. In this aspect, the first transition metal oxide and the second transition metal oxide are different from each other, the metal oxides are bonded together using a binder, the first layer further comprises a titanium suboxide, the second layer further comprises a cobalt suboxide, and the energy harvester generates an electric current in the presence of oxygen and water vapor.

[0088] Further aspects provide solid-state energy harvesters having carbon added to the first and third layers to enhance conductivity while leaving the second layer unchanged, thereby allowing separation of charge across the relatively small conductivity of the separator layer.

[0089] In another aspect, a method of making a solid-state energy harvester is provided, the method comprising milling a first mixture comprising a first transition metal suboxide, a solid electrolyte comprising a lanthanide and the first transition metal suboxide, and a binder to form a first layer; milling a second mixture comprising a solid electrolyte comprising a lanthanide and a binder to form a second layer; milling a third mixture comprising a second transition metal suboxide, a solid electrolyte, and a binder, and forming a third layer; and connecting the first layer to the second layer, and connecting the second layer to the third layer. In this aspect, the first layer is an anode, and the second layer is an SSE separator, and the third layer is a cathode, and the first transition metal suboxide and the second transition metal suboxide are different from each other.

[0090] The first transition metal suboxide and the second transition metal suboxide may each be independently selected from the group consisting of tungsten suboxide, cobalt suboxide, Co3O4, Na 1.0 Mo 1.5 WO 6.0 、Na0.9 Mo6O 17 、Na 1.0 Ti 1.5 WO 4.5 、Na 1.2 Ti 0.34 WO4, Ti4O7, Ti5O9, K 1.28 Ti8O 16 , K 1.04 Ti8O 16 , K 0.48 Ti8O 16 、Na4WO3、Na 0.90 WO 1.81 、Na 0.82 WO 1.81 、Na 0.74 WO 1.81 , K 0.9 WO3、WO 2.72 , WO 2.82 , WO 2.9 、Na2WO4、Na 8.2 WO, Na2O2WO3, Na 1.2 Ti 0.34 WO4、Na 1.2 Cu 0.31 WO 7.2 、Na 1.2 Mo 0.31 WO 5.2 and Na2O4WO3.

[0091] The first mixture, the second mixture, and the third mixture can be ground in a high shear, high intensity blender.In another aspect, the first layer, the second layer, and the third layer are not separated by a physical separator.

[0092] In further aspects, the first transition metal suboxide and the second transition metal suboxide are each selected from the group consisting of titanium, cobalt, tungsten, or cesium.The first transition metal suboxide may include titanium suboxide.

[0093] In yet another aspect, water can be added to the first mixture, the second mixture, and the third mixture before grinding. In another aspect, the first mixture has no more than about 10% water, and the second mixture and the third mixture have no more than 5% water. In one aspect, the first mixture and the second mixture each have a water content of less than about 10% or less than about 25 weight percent. In yet another aspect, each of the first layer, the second layer, and the third layer has a water content of less than about 5 weight percent.

[0094] In another aspect, the second transition metal suboxide comprises a cobalt suboxide. In a further aspect, each of the first layer, the second layer, and the third layer comprises a solid electrolyte comprising a tungsten suboxide and ceria.

[0095] In yet another aspect, each of the first binder, the second binder, and the third binder is selected from the group consisting of unsintered polytetrafluoroethylene (PTFE), FEP, paraffin wax, and epoxy resin.

[0096] In further aspects, each of the first binder, the second binder, and the third binder is less than about 50 volume percent of each of the first layer, the second layer, and the third layer.

[0097] In another aspect, the method of making a solid-state energy harvester further includes compressing the first mixture, the second mixture, and the third mixture, or a combination of the first mixture, the second mixture, and the third mixture in a roller mill to produce a back-extrusion.

[0098] In another aspect, the anode comprises about 17% (w / w) CeO2, 33% (w / w) WO 2.9 , 50% (w / w) Ti4O7 and 40 volume percent of powdered PTFE.

[0099] In one aspect, the cathode comprises about 17% (w / w) CeO2, 33% (w / w) WO 2.9 , 50% (w / w) Co3O4 and 40 volume percent of powdered PTFE.

[0100] In yet another aspect, the anode comprises about 17% (w / w) CeO2, 33% (w / w) WO 2.9 , 50% (w / w) Ti4O7 and 40 volume percent of powdered PTFE; the solid electrolyte (SSE) contains about 67% (w / w) WO 2.9 , 33% (w / w) CeO2 and 40 volume percent of powdered PTFE, and the cathode contains about 17% (w / w) CeO2, 33% (w / w) WO 2.9 , 50% (w / w) Co3O4 and 40 volume percent of powdered PTFE.

[0101] In another aspect, each of the first layer, the second layer, and the third layer comprises Teflon particles, each of the first binder and the second binder comprises a powder, and each of the first layer and the second layer is manufactured using a roller mill to force the powder through the rollers of the mill and extrude the Teflon particles into fibrils.

[0102] In one aspect, the solid-state energy harvester is enclosed in a non-conductive, substantially gas-impermeable housing. The non-conductive, substantially gas-impermeable housing may have a gas inlet and a gas outlet on opposite sides of the housing. The non-conductive, substantially gas-impermeable housing may be made of a material selected from the group consisting of polyacrylates and polycarbonates. The term non-conductive refers to a material that does not conduct electrons. The term "substantially gas-impermeable" refers to a material that does not allow a substantial portion of gas to pass through (less than 1% gas leakage) in any environment during the time the battery is in operation.

[0103] Another aspect provides a solid-state energy harvester comprising: an anode comprising a first transition metal suboxide; a separator comprising a solid electrolyte (SSE) comprising a mixture of a second transition metal suboxide and a lanthanide oxide or a lanthanide dioxide; and a cathode comprising a third transition metal suboxide.

[0104] In another aspect, the first transition metal suboxide, the second transition metal suboxide, and the third transition metal suboxide are different from one another.

[0105] In one aspect, the anode and cathode further comprise carbon (eg, carbon black or graphite). The amount of carbon in the anode may be from about 2% to about 6%. In another aspect, the amount of carbon in the anode is 3%.

[0106] In another aspect, the separator further comprises Ti4O7.

[0107] In yet another aspect, a solid-state energy harvester can be used as an energy storage unit (eg, battery, capacitor), or connected to at least a second energy storage unit or an array of energy storage units.

[0108]

[0013] Additional aspects provide a double-layer solid-state energy harvester comprising: a first layer comprising a first transition metal suboxide and a solid state electrolyte (SSE), and a second layer comprising a second transition metal suboxide and the SSE, wherein the first transition metal suboxide and the second transition metal suboxide are different from each other.

[0109] In another aspect, the first layer of the solid-state energy harvester is separated from the second layer by a conductive metal (e.g., gold) layer. The term "conductive metal" refers to a metal that allows electric current to flow in one or more directions with low resistance. The conductive metal can be an expanded metal (e.g., nickel, gold, titanium, carbon brass, copper, etc.).

[0110] Yet another aspect provides a method of making a dual-layer solid-state energy harvester by: milling a first mixture comprising a first transition metal suboxide, a solid electrolyte comprising a lanthanide element and the first transition metal suboxide, and a binder to form a first layer; milling a second mixture comprising a second transition metal suboxide, a solid electrolyte, and a binder, and forming a second layer; and connecting the first layer to the second layer, wherein the first layer is an anode and the second layer is a cathode, and the first transition metal suboxide and the second transition metal suboxide are different from each other.

[0111] Transition Metal Suboxides and Defect Theory

[0112] The general theory described herein is applicable to exemplary active components in energy harvesters, such as Ti4O7, WO 2.9 , Co3O4 and CeO2. Members of the non-stoichiometric metal oxide suboxide phases exhibit lower band gaps and resistivities, with the highest electrical conductivity. These phases have high oxygen vacancies, and the electronic connectivity increases with increasing oxygen vacancies. The electrons from the d orbital split into two components with different energies, called t2g and eg orbitals. The electron conduction path can be switched back and forth by the drift of the charged oxygen vacancies. The conductivity in the conduction band can be caused by these oxygen vacancies and / or metal-induced defects. It is believed that hypo-stoichiometry can be caused by oxygen vacancies or metal interstitials, as represented in the Kroger–Vink notation by the following two redox reactions, respectively:

[0113] and

[0114] See, for example, Zhang et al., “The role of single oxygen or metal induced defectand correlated multiple defects in the formation of conducting filaments”, Department of Precision Instrument, Centre for Brain Inspired Computing Research, Tsinghua University, Beijing, China, which is incorporated herein in its entirety.

[0115] These equations allow charge motion reactions, for example, to be described individually as:

[0116] O x o +h· -->O · 0

[0117] Among them, x o It represents the oxygen ion located at the oxygen lattice position, with a neutral charge, h · represents an electron hole, and O · 0 represents a singlet oxygen atom with a single charge. In addition,

[0118] Ce x ce +e - -->Ce' ce’

[0119] Among them, Ce x ce represents the cerium ion located in the cerium lattice position, with a neutral charge, and Ce' ce’ Represents the cerium anion in the interstitial position, which carries a single negative charge.

[0120] This is an exemplary description of how a neutrally charged cerium ion at a cerium lattice site can accept an electron and become a charged cerium ion at that lattice site, and how charge is transferred in the solid-state electrolytes described herein.

[0121] See also, “Solid state aspects of oxidation catalysis” by Gellings et al., Laboratory for Inorganic Materials Science, University of Twente, PO Box 217, NL-7500AE Enschede, The Netherlands, (2000), which is incorporated herein in its entirety.

[0122] For proton defects in oxides, an illustrative formation reaction between a water molecule and an oxygen vacancy is as follows:

[0123] O O x +V O ·· +H2O(g)→2OH O ·

[0124] In this reaction, two effective positive hydroxyl-groups are formed at regular oxygen positions. Additional defect reactions to form proton defects by reaction with hydrogen are described below. The reaction with electron holes is as follows:

[0125] 2h · +2O O x +H2→2OH O ·

[0126] Where the presence of excess holes is required. Alternatively, the oxidation of hydrogen under the formation of free electrons is exemplified by the following reaction:

[0127] 2O O x +H2→2OH O · +2e′

[0128] The electrons are assumed to contribute to the conduction band.

[0129] Gellings et al. proposed that at low temperatures, the dissolution of water in the Li / MgO catalyst occurs via reaction with oxygen or with oxygen vacancies as shown in the following equation:

[0130] and

[0131] At low temperatures (e.g. 673 K), the conductivity is found to be dominated by OH as the main charge carrier. O · ions. This shows the importance of water in transporting charge in both the Ti4O7 anode and the CeO2 solid-state "electrolyte".

[0132] It has been theorized that CeO2 can store and transport oxygen, and in its reduced state, CeO2 decomposes water to release hydrogen as shown in the following equation (see B. Bulfin et al., Analytical Model of CeO2 Oxidation and Reduction, School of Physics, Trinity College Dublin, College Green, Dublin 2, Ireland, J. Phys. Chem. C, 2013, 117(46), pp. 24129-24137, DOI: 10.1021 / Jp406578z, Publication Date (Web): October 16, 2013, incorporated herein in its entirety).

[0133]

[0134] and

[0135] CO 2-δ +δH2O→CO2+δH2

[0136] Bulfin et al. explain the relationship between ceria and its suboxide states, and the resulting activity of these molecules, primarily relevant to the manufacture of synthetic fuels and catalytic converters. The relationship described by Bulfin et al. uses the Arrhenius equation, which teaches that the rate constants of most chemical reactions increase by the negative power of the reciprocal of the absolute temperature. According to Bulfin et al., this effect is shown above 500°C. However, many of the graphs in Bulfin et al. show that some activity occurs at ambient temperatures.

[0137] In one aspect, the energy harvester described herein has five components: WO 2.9 , CeO2, Co3O4, Ti4O7 and unsintered PTFE powder. Table 1 below shows the composition of exemplary aspects, where the percentages are weight percentages, except that the PTFE binder is given in volume percentage. Components 1 and 2 in Table 1 are components of the solid electrolyte (SSE), component 3 is the active ingredient of the anode, and component 4 is the active component of the cathode. PTFE is a binder. The three electrodes shown in Table 1 include a titanium-containing anode, a separator and a cobalt-containing cathode. The moisture values ​​are measured and the percentages are determined by the results of several factorial experiments shown in Table 1 below. The "separator" layer can be omitted from the design, resulting in a dual electrode design.

[0138] Table 1

[0139]

[0140]

[0141] In one aspect, cerium dioxide (CeO2) and tungsten suboxide are used as solid electrolytes. In this aspect, tungsten suboxide is WO 2.9 In this aspect, the composition is 1 part CeO2 and 2 parts WO 2.9 The ratio exists.

[0142] Ceria is a large molecule (MW = 172.12) in which the oxygen atoms are on the outer part of the crystal structure. The oxygen atoms are loosely attached and therefore move easily from one molecule to the next. Figure 1 , there are shown cerium atoms 101 and oxygen atoms 102. Without being bound by theory, it is believed that the difference in atomic size between the cerium atoms 101 and the oxygen atoms 102 allows the oxygen atoms to move around relatively freely and catalyze the redox reaction. Figure 1 The diagram shows how an exemplary oxygen atom is loosely attached to the large lanthanide element cerium.

[0143] In another aspect, the energy harvester contains a low percentage of water. The neutral water used in the above equation has a mass of 1×10 -7 The molar concentration of H+ and OH — ions, and is exemplified by:

[0144] H2O-->H + +OH —

[0145] 2H2O-->2H2+O2

[0146] CeO2 as described in Zhang can catalyze this reaction. While not wishing to be bound by theory, the following two mechanisms may be relevant.

[0147] Mechanism 1

[0148] The use of CeO2 as a catalyst with mobile oxygen atoms is described in an article on catalytic converters in trucks, G. Ranga Rao et al. "Structural, redox and catalytic chemistry of ceria based materials", Bulletin of the Catalysis Society of India (2003) 122-134, which is incorporated herein in its entirety. CeO2 as a catalyst is used to catalyze the conversion of methane gas into CO2 and water, as well as other pollutant purification catalysis.

[0149] The following equation (such as Figure 2 The steps of the process are shown in Figure 2, where 201 = Ce4+, 202 = O2-, 203 = vacancy, and 204 = Ce3+, where V = vacancy:

[0150] H2+Ce +4 4O -2 4<- Step 1 -> Equation 3

[0151] Ce +4 4O -2 4H2<-Step 2-> Equation 4

[0152] Ce +4 2Ce +3 2O -2 3H + V+OH - <-Step 3-> Equation 5

[0153] Ce +4 2Ce +3 2O -2 3V+H2O<-Step 4-> Equation 6

[0154] Ce +4 2Ce+3 2O -2 3V Equation 7

[0155] The overall equation is:

[0156] H2+Ce +4 4O -2 4-->Ce +4 2Ce +3 2O -2 3V Equation 8

[0157] Mechanism 2

[0158] Cerium dioxide (CeO2) is well known for its oxygen mobility. CeO2 undergoes rapid redox cycles, for example:

[0159] 2CeO2-->Ce2O3+1 / 2O2 Equation 9

[0160] Ce +4 -->Ce +3 Eo=1.61

[0161] Ceria due to redox Ce +4 / Ce +3 Acts as an oxygen buffer by storing / releasing O2. This is a reversible reaction, making it an oxygen storage material. In oxygen-free conditions (e.g., under argon), the reaction moves in the opposite direction. This promotes other electrode reactions with Ti4O7 and Co3O4, as discussed below.

[0162] Without wishing to be bound by theory, the actual mechanism is most likely some combination of the two pathways discussed above, combined with the "defect theory" described above.

[0163] Interaction of dissolved oxygen with water

[0164] In another aspect, the energy harvester preferably contains a small amount of water in the electrodes, which triggers a response to the presence of oxygen - or conversely, to the removal of oxygen by flooding with argon (0% oxygen). Oxygen does not ionize when dissolved in water, but is held between water molecules, such as Figure 3, where rectangles 301 highlight water molecules (oxygen 102 and hydrogen 302) and do not represent entities within them and themselves. The oxygen molecules (303) become closely associated with the retention of oxygen diatomic molecules and are therefore closely associated with the transport of those molecules from place to place (place-to-place). In conventional energy harvesters, this can be considered an "electrolyte", but in the present energy harvester, the electrodes can be separated by nickel expanded metal, so the transport of charge is within the electrodes, rather than between them. Combined with the understanding of defects in the suboxide crystal structure in the above paragraph, one aspect of charge transport is the free flow of charge with relatively small amounts of water.

[0165] In some aspects, the anode may contain between 0.01% and 15% water. In other aspects, the anode may contain between 0.1% and 10%, between 1% and 8%, or between 2% and 5% water. In some aspects, the second layer may contain between 0.01% and 8% water. In other aspects, the second layer may contain between 0.1% and 5%, between 1% and 4%, or between 2% and 3% water. In some aspects, the cathode may contain between 0.01% and 5% water. In other aspects, the cathode may contain between 0.1% and 10%, between 1% and 8%, or between 2% and 5% water.

[0166] In one aspect, WO 2.9 The separator and CeO2 spacer are located between the anode and cathode to allow the transfer of charge on the oxygen atoms. The intermediate layer contains tungsten suboxide (WO 2.9 ) mixed with cerium dioxide, and in one example, with uniform weight. Tungsten has many oxidation states, but +6 and +4 are the most stable. WO 2.9 The valence of tungsten is given as +5.8, which is the average value for the crystal. 2.9 Available from Global Tungsten (gobaltungsten.com).

[0167] Figure 4 Shows WO 2.9 The crystal structure and the effect of dehydration on charge transport. The octahedron shown as 401 is a tungsten orbital field, the larger black dots 301 represent water molecules, the smaller black dots 102 represent singlet oxygen in the crystal, and the smaller light dots 302 represent hydrogen atoms. Without wishing to be bound by theory, it is believed that Figure 4 The water molecules shown in allow for greater mobility of the WO3 crystal components. x (Also denoted as WO 3-x ) the same structure exists, but some of the charge-carrying oxygens are missing from the material of the crystal. Figure 4The figure shows the effect on the crystal structure as the crystal dehydrates from "a" with ample water molecules 301 to slightly dehydrated "b" and finally fully dehydrated "c". In one aspect, the energy harvester is fabricated in the dehydrated "c" state and then allowed to spontaneously hydrate in situ through "b" to "a".

[0168] The following reaction scheme is illustrative:

[0169] Restore("V" = "Vacancy")

[0170] 2(W +6 –O–W +6 )+4e - +O2--> Equation 10

[0171] 2(W +5 –V–W +5 )2(O)+4e - --> Equation 11

[0172] 2(W +5 –O–W +5 )+4e - Equation 12

[0173] Total: 2(W +6 –O–W +6 )+O2-->2(W +5 –O–W +5 )+2e -

[0174] Oxidation

[0175] 2(W +5 –O–W +5 )+O2--> Equation 13

[0176] 2(W +6 –O–W +6 )+(O)+2e - --> Equation 14

[0177] 2W +5 +O2-->Equation 15

[0178] (W +6 –O–W +6 )+(O)+2e - Equation 16

[0179] W +6 -->W +4 (W +6 -->W +5 Unknown) o ~+ / -0.91 volts

[0180] E o Source: http: / / hyperphysics.phy-astr.gsu.edu / hbase / Chemical / electrode.html

[0181] Total: 2(W +5 –O–W +5 )+O2-->2(W +6 –O–W +6 )+2(O)+2e - Equation 17 The sum of the partition reactions

[0182]

[0183] and

[0184]

[0185] as well as

[0186]

[0187] In one aspect, oxygen enters the separator, and both singlet oxygen and electrons leave to move into the anode. In this aspect, singlet oxygen reacts with ceria to transfer more electrons. Water can have a catalytic effect in these events.

[0188] In one aspect, the active component of the cathode is cobalt (II, III) suboxide (Co 3 O 4 ). Figure 5 The crystal structure of Co3O4 is shown, where Co +2 Shown as sphere #2 (501), Co +3 is shown as sphere #3 (502), and the oxygen atoms are the light colored sphere #1 (202). Cobalt has two oxidation states, +2 and +3, both of which are present in this crystal. The oxygen atoms are loosely bound to the large cobalt atoms and are electronegative compared to the Ti4O7 anode. The mixing of CeO2 with Co3O4 allows for the dispersion of the charge carrying oxygen atoms, reducing the valence of cobalt from +2 & +3 in Co3O4 to only +2 in CoO, releasing the oxygen atoms into the oxygen pool associated with CeO2.

[0189] Depending on the direction of oxygen concentration, the above reaction results in reversible redox release or absorption of oxygen by CeO2-Co3O4 crystallites, as shown by the following root equations:

[0190] O2+4e - -->2O -2 Equation 19

[0191] 2Co3O4-->6CoO+O2 Equation 20

[0192] Adding these two equations (via Cations reduced at the cathode):

[0193] 2Co3O4+4e - -->6CoO+O -2 Equation 21

[0194] According to equation 9 above:

[0195] 2CeO2-->Ce2O3+1 / 2O2 Equation 9

[0196] Adding Equation 21 to Equation 9 gives:

[0197] Co3O4+4e - +2CeO2-->3CoO+O -2 +Ce2O3+1 / 2O2 Equation 22

[0198] Looking at cations only:

[0199] Co +2.67 +Ce +4 -->Co +2 +Ce +3 +1.76e - E o ~1.715

[0200] The above description is an example of how oxygen atoms can flow freely from one cation to another charge-carrying cation in the aspects described herein.

[0201] In one aspect, the active component of the anode is Ti4O7 (also denoted as Ti n O 2n-1 ), where n is between 4 and 10. Ti n O 2n-1 is a member of the non-stoichiometric titanium oxides known as phase, which exhibits a lower band gap and resistivity and has the highest conductivity reported for Ti4O7. The atomic structure of the molecule is shown in Figure 6 , where the titanium atoms are shown as "Ti1"-"Ti4" for each titanium atom (601-604) in each Ti4O7 molecule, and oxygen is shown as an "O" atom (102). For Ti4O7, titanium has a valence of +3.5, which is an average value for the crystal because the valence state must be an integer. When electrons flow in through the separator, the Ti4O7 molecule transfers the electrons to the The anode conduction band in the phase and then enters the anode current collector electrode.

[0202] These equations can be summarized as follows:

[0203] H2O-->H + +OH — Equation 23

[0204] 4Ti2O3+2OH - +2O -2 -->2Ti4O7+H2O+2e - Equation 24

[0205] According to Equation 9 above (expressed in anodic form):

[0206] Ce2O3+1 / 2O2-->2CeO2 Equation 9

[0207] Adding Equation 12 to Equation 9 gives:

[0208] 4Ti2O3+2OH - +O -2 +2Ce2O3+O2-->2Ti4O7+H2O+4CeO2+2e - Equation 24 looks at only the cation:

[0209] Ti +3 +Ce +4 -->Ti +3.5 +Ce +3 E o ~1.085

[0210] Full Energy Harvester Flow:

[0211] Cathode: Co3O4+2e - +4CeO2-->3CoO+2Ce2O3+O2+1 / 2O2

[0212] Anode: 4Ti2O3+2OH - +O -2 +2Ce2O3+O2-->2Ti4O7+H2O+4CeO2+2e -

[0213] Overall: Co3O4+4CeO2+4Ti2O3+2OH - +2H + +1 / 2O2+2Ce2O3-->3CoO+2Ce2O3+2Ti4O7+2H2O+4CeO2

[0214] Thus, oxygen and water (which dissociate) enter the cathode, and the final acceptor for the oxygen is the hydroxyl ion which produces water vapor.

[0215] Table 2 below shows the relevant potentials, which are related to Fig.10 The potentials observed in the OCV experiments shown are similar.

[0216] Table 2

[0217]

[0218] Sources of materials used:

[0219] Ti4O7, Ti-Dynamics Co.Ltd, Magnéli Phase Titanium Suboxide-N82, www.Ti-dynamics.com

[0220] WO 2.9 , "Tungsten Blue Oxide" http: / / globaltungsten.com#P005016

[0221] Co3O4 Cobalt (II, III) oxide, www.fishersci.com#AAA1612130

[0222] CeO2 Cerium(IV) Oxide, www.fishersci.com#AC199125000,

[0223] Teflon 30 dispersion “DISP 30”, www.fishersci.com #501090482 or www.chemours.com.

[0224] PTFE 7CX: www.chemours.com

[0225] DAIKIN F104 Unsintered Teflon Powder

[0226] CABOT Vulcan XC72R (GP-3875) Carbon V72

[0227] ASBURY Graphite Mills "Nano 307"

[0228] Cross-bonded expanded metal 4Ni 5-060 P&L x 4: Dexmet Corporation, 22 Barnes Industrial Rd S, Wallingford, CT 06492 (www.dexmet.com)

[0229] Nickel 10mil Shim Stock, (www.mcmaster.com) #9707K79

[0230] 3 / 4” Silver bezel: (www.riogrande.com) #950272

[0231] 24kt gold cyanide plating solution: (www.riogrande.com)#335082

[0232] 24kt gold sheet for anode: (www.riogrande.com)#608030

[0233] Roller mill manufactured by Durston (www.durston.co.uk, #DRM F130R)

[0234] Example 1: Pellet Electrode

[0235] The pellet electrode was manufactured as follows.

[0236] Weigh the powder: anode is 17% CeO2, 33% WO x , 50% Ti4O7; solid separator is 33.3% CeO2 and 66.7% WO x ; The cathode is 17% CeO2, 33% WO x and 50% Co3O4; the binder is 40% Teflon 7c by volume.

[0237] Mix the powders in a high intensity blender. Prepare a 3 / 4" compression cylinder and lubricate it with a small amount of Polymist F-5AEx by Ausimont sintered Teflon powder. Place a 3 / 4" cross-bonded expanded metal disc (Dexmet Corp, 4Ni 5-00P&L x 4) at the bottom of the compression cylinder. Pour the blended powder into the cylinder. Add another 3 / 4" cross-bonded expanded metal disc on top of the powder. Place a stainless steel cover plate on the cylinder. Compress to 5000 pounds (11,318 psi) and hold for a few seconds. Remove from the cylinder and measure and record the weight and thickness.

[0238] Knowing the densities, weights and volumes of all components are used to calculate the porosity of the resulting pellet. A pressure is selected that provides good bonding of the powders and good porosity. In this example, 5000 pounds was found to be an exemplary pressure.

[0239] The pellets were then placed in a humidity chamber at 100% relative humidity for four days to bring the internal water content to about 5% in the anode, about 3.5% in the separator, and about 0.6% in the cathode.

[0240] Fig. 7A The physical layout of an exemplary resulting energy harvester is shown with three electrodes: anode pellets (7A1), separator pellets (7A2), cathode pellets (7A3), and nickel cross-bonded expanded metal (7A6) between each layer, with the anodes embedded in a gold frame (7A4) secured with epoxy adhesive (7A5). Each pellet also has nickel expanded metal (7A6) on each surface.

[0241] The separator pellet (7A2) is often omitted from the design, resulting in a two-electrode design.

[0242] Example 2A: Roller Electrode

[0243] An embodiment of a roller electrode is manufactured as follows:

[0244] Weigh the powder: anode is 17% CeO2, 33% WO x , 50% Ti4O7; solid separator is 33.3% CeO2 and 66.7% WO x ; The cathode is 17% CeO2, 33% WO x and 50% Co3O4; the binder is 40% Teflon 7c by volume. Mixed in a high intensity blender.

[0245] A 60 mm diameter precision roller mill manufactured by Durston (www.durston.co.uk, #DRM F130R) is adjusted to a gap of 0.178 mm (0.007"). The rollers must be highly parallel. With the rollers in a horizontal position, the powder is poured onto the roller nip. The rollers are slowly rotated toward the nip, drawing the powder into the nip and producing a self-supporting sheet on the underside of the roller. The sheet is removed and placed on a clean sheet of paper. Disks of each sheet are cut using an arched punch, such as a 3 / 4" (19 mm) diameter punch #3427A19 from McMaster Carr. In one aspect, the diameter of the cathode is 1", the diameter of the separator is 7 / 8", and the diameter of the anode is 3 / 4", to ensure that there is no cross-electrode shorting. In more elaborate production situations, the diameters can be the same.

[0246] Place the cathode sheet on a current collector (e.g., gold or gold-plated nickel or other metal). An intra-electrode current collector may or may not be used on this first sheet. If an intra-electrode current collector is used, a 10 mil nickel liner, flat nickel expansion metal, or no spacer may be used (sheets in direct contact). Follow the protocol for the current collector, placing the separator sheet first, then the anode sheet. Place the current collector on the anode.

[0247] The resulting energy harvester is assembled into a test apparatus and compressed, for example, using a 40-psi force.

[0248] Figure 7B The physical layout of a three-electrode, thin roller energy harvester is shown. This embodiment does not use metal spacers. Figure 7B In the example, there is an anode layer 7A1, a separator layer 7A2, and a cathode layer 7A3 sandwiched between an anode current collector 7B1 and a cathode current collector 7B2. None of these exemplary energy harvesters contain an insulating separator as most liquid electrolyte energy harvesters do.

[0249] The separator layer (7A2) is often omitted from the design, resulting in a two-electrode design.

[0250] Example 2B: Roller Electrode

[0251] To solve the roller adhesion problem described above, another embodiment of the roller electrode is manufactured as follows:

[0252] Weigh the powder: anode is 17% CeO2, 33% WO x , 50% Ti4O7; solid separator is 33.3% CeO2 and 66.7% WO x ; The cathode is 17% CeO2, 33% WO x and 50% Co3O4; the binder is 40% Teflon 7c by volume. Mixed in a high intensity blender.

[0253] A 60 mm diameter precision roller mill (DRM F130R, manufactured by Durston) was used in a vertical position. Figure 8 801). Cut two pieces of 1 / 16" (1.58 mm) sintered Teflon sheet (McMaster Carr #8545K13) or thicker, about 100 mm wide (about 4 inches) and about 150 mm long (about 6 inches) (802). The roller mill gap is adjusted to twice the thickness of the Teflon sheet plus .007" (0.178 mm). Optionally, the rollers can be pressed together pneumatically rather than at a constant gap. In this way, the thickness of the powder entering the mill can vary more than when a constant gap is used. A pair of 4-inch flat cylinders (Mead Fluid Dynamics SS-400X1.125-FB) giving 1257 pounds of force at 50-psi can be used. About 25 psi (630 pounds of force) can be used to produce a strong sheet while keeping the porosity within a useful range (e.g., 0% to about 50% porosity).

[0254] The fully blended powder is poured onto one sheet (803), scraped between stainless steel bars to a constant thickness and width, and the second sheet is placed on top. The rollers are slowly rotated toward the nip, drawing the Teflon sheet and powder into the nip and creating a self-supporting sheet between the Teflon sheets. For example, the Teflon sheet (802) can be replaced with a Teflon-coated metal sheet of the same size cut from a cookie sheet. Remove the electrode sheet (804) using a safety razor or other sharp tool and place it on a clean sheet of paper. Using an arch punch, such as a 3 / 4" (19 mm) diameter punch (e.g., #3427A19 from McMaster Carr), cut disks from each sheet. Place the cathode sheet on a current collector (e.g., gold-plated brass or nickel). Optionally, a current collector may be used on this first sheet. A 10-mil nickel liner, flat nickel expanded metal, or no spacer may be used (sheets in direct contact). Following the protocol for the current collector, place the separator sheet first, then the anode sheet. Place the current collector on the anode; here, a gold-plated nickel or brass liner is used. Assemble the resulting energy harvester into a test apparatus, for example, by compression using a 40-psi force.

[0255] In another aspect, the diameter of the cathode is 1", the diameter of the separator is 7 / 8", and the diameter of the anode is 3 / 4". In this aspect, cross electrode shorting is reduced or eliminated. In another aspect, the diameters can be the same.

[0256] The separator layer may be omitted, with the anode and cathode simply placed in direct contact with each other. In another aspect, the anode and cathode have a concentration gradient of material to produce, for example, a higher impedance near the interface between the electrodes.

[0257] In some aspects having carbon (graphite or carbon black) added to the anode and cathode electrodes, no additive is added to the SSE layer located between the anode and cathode. In this aspect, separation of charge is achieved by using the higher impedance of the SSE layer. In other aspects, no load can be lower than the total output impedance of the finished unit.

[0258] In many energy harvester configurations, the battery is placed within a plastic housing. Exemplary plastic housings are made of polyacrylates and polycarbonates, but may comprise any non-conductive plastic material. The adhesive used is "airplane glue" when polycarbonate is used, or methyl ethyl ketone (MEK) when polyacrylate is used. In one aspect, the functional cell is enclosed in a space with a gas inlet and outlet for increased control of the gas reactants and to make the resulting cell more robust. When a housing is used, the gas is pumped across the electrodes at a rate from 5 ml / min to 300 ml / min, depending on the test involved, with an exemplary rate of 50 ml / min per cell.

[0259] Example 3: Testing

[0260] The test equipment holds the energy harvester under 125 pounds of force on the anode and cathode collectors, which are gold-plated nickel 200 or brass, which rest on a cast acrylic stand. Testing is performed using a Solartron S1287 electrochemical interface and a Solartron S1250 frequency response analyzer, but many other test equipment may work. The pellets are tested as individuals and as energy harvesters between gold electrodes. The entire device is located inside a plastic bag for gas environment experiments. Typically, testing can be performed in air (20% O2), 100% O2, and argon (0% oxygen). When testing the assembled energy harvester, the cathode is used as the working electrode and working reference. The anode is the counter electrode and reference electrode. In this example, one would expect a negative current when the energy harvester is short-circuited or discharged at a constant potential.

[0261] When the energy harvesting cell is built into a gas-tight enclosure, the gas is then delivered to the cell via a port at one end of the enclosure, where the gas escapes out the exhaust port. Typically, testing is done in air (20% O2), 100% O2, and argon (0% oxygen).

[0262] The test included the following setup:

[0263] - Open circuit voltage (OCV) for 1 minute

[0264] - AC impedance spectrum from 1 MHz to 1 mHz with 10 data per decade.

[0265] - Normalize to units of physical conditions by measuring the thickness of the compressed electrode or pellet thickness and knowing the surface area.

[0266] - Polarization curve from OCV to zero volts.

[0267] - This gives us the exchange potential (E o ), limiting current density and power density.

[0268] - Cyclic voltammogram from OCV to +1.0 volt, to -1.0 volt, five times at 50mV / sec. The data obtained include:

[0269] -R 功能 , by taking the maximum current at +1 volt and the minimum current at -1.0 volt, and calculating the slope between these two points as the resistance (R 功能 =dV / di).

[0270] -Hysteresis at 0 volts: If electrons are consumed and released during cycling, as in the case of an electrochemical or capacitive system, there is a spread of current when the direction of the potential is up rather than down. Essentially, the electrons are consumed or released rather than simply passing through the system (as they would through a resistor). The greater the hysteresis, the better the crystal is for storing or releasing energy. The distribution of current density in the positive and negative directions is the hysteresis, which can be measured as the voltage at zero current.

[0271] Embodiment 4:

[0272] CeO2 is used in equal parts in all three electrodes: Ti4O7 anode, WO 2.9 Separator and Co3O4 cathode. CeO2 was mixed with 10% Teflon 7c from DuPont. Each pellet contained 2 grams of active material and pure nickel expanded metal (from Dexmet) on both surfaces. The pellets were made as described above and kept in 100% relative humidity for four days, which gave a moisture content of 3.7% for the anode, 1.6% for the separator, and 0.5% for the cathode pellet. To assemble the energy harvester, the anode pellet was adhered to a heavily gold-plated silver frame with 5 minutes of epoxy at its periphery while being kept under 40PSI compression to ensure good contact with the gold. The separator was sealed with epoxy around its periphery; this ensured that all oxygen must be transmitted from the cathode through the separator.

[0273] As above Fig. 7A The energy harvester of this pellet design described in was then completely short-circuited for one hour and allowed to recover in eight cycles for one hour in an oxygen environment. The chamber was not hermetically sealed, so oxygen diffused out, and nitrogen diffused in, but at a very low rate. Fig. 9The current density during the short circuit is shown for many of the discharges. It should be noted that all of the discharge tests have inverted vertical axes, since the cathode is considered the working electrode, the current is negative and the open circuit voltage will be positive. During the top two lines (A), oxygen was introduced at about 700 seconds, and another at about 1600 seconds, oxygen was reintroduced and a jump in performance was recorded. All other lines are in air (20% oxygen).

[0274] After each short circuit described above, the energy harvester was allowed to sit in oxygen for one hour. Fig.10 The energy harvester recovers consistently after a dead short - even after 25 hours of continuous shorting.

[0275] Next, the energy harvester was allowed to sit in the different atmospheres. Fig.11 The results of this experiment are shown. The energy harvester was started in air (20% oxygen), then after about 5 minutes, the atmosphere was changed to pure oxygen and the current density increased from about 30 mV to about 70 mV. Then, at about 20 minutes, the atmosphere was changed to pure argon (0% oxygen), and the potential dropped to zero and then even below zero. Next, at about 4 hours, the atmosphere was returned to open air (20% oxygen) and the potential returned to about 45 mV. This shows the strong influence of the external gas on the performance of this energy harvester.

[0276] Next, a complete short circuit was performed in various gases, and Fig.12 The resulting current density under the three gas environments is shown in a bar graph. The current is cathodic, resulting in a negative value, so it needs to be multiplied by -1, as Fig.12 A strong influence of the presence of an atmosphere of air is visible in the first column, then in oxygen (second column) and finally in argon (0% oxygen) (third column).

[0277] Fig.13 A voltammogram of energy harvester 28716.4 (Oct. 14, 2016, cell #4) is provided, showing that after the energy harvester is allowed to sit in air for 48 hours, 170 uA / cm 2 The voltammogram also shows that at 0.066 volts, 5 nW / cm 2 . This data is not impedance compensated.

[0278] Fig.14 The AC impedance of the energy harvester is shown to be acceptably low. Compression of the pellets and current distribution of the nickel cross-bonded expanded metal both contribute to the impedance problem. Fig.15is the Nyquist plot of the energy harvester, which shows a large charge transfer resistance (R ct ).

[0279] Example 6: Excluding Water as Liquid Electrolyte

[0280] To test whether water is a liquid electrolyte, insert Fig.16 An energy harvester was constructed by placing five (5) layers of dry nickel expanded metal between electrodes, showing the anode (7A1), five expanded metal disks (1601), a separator pellet (7A2), another five expanded metal disks (1601), and a cathode pellet (7A3). The source of the electrodes was the well-tested energy harvester above. The anode and separator were then re-epoxy sealed (7A5) while under pressure, preventing any external contact with air, leaving the cathode pellet (7A3) exposed to air. The energy harvester was reassembled and tested. In this embodiment, electrons and gases rather than ions were allowed to pass between the electrodes. The pellets were manufactured according to Example 1 above.

[0281] Fig.17 Two voltammograms of these energy harvesters 30616.1 are shown (November 2, 2016, cell #1). The top line is the case where the electrodes are embedded together, and the bottom line shows the performance with 5 expanded metal disks separating each electrode. The energy harvester can perform even without any possible ion movement between the electrodes, demonstrating that such ion movement is not required, and that charge is indeed transferred via electrons and possibly on charged gas molecules, but not as ions.

[0282] Fig.18A and Fig.18B is a graph of a set of short circuit discharges and OCV spontaneous recharges, all done in air (20% oxygen). Fig.18A The discharge setup is shown in Figure 1, where the top line is an energy harvester with electrodes in close contact, and the lower set of lines shows the performance with five layers of expanded metal placed between the electrodes. Obviously, the performance continues without ion transport, but only electrons and possibly also charged gases.

[0283] Fig.18B is the same setup, but for voltage recovery after a one hour discharge. Again, the top line is an energy harvester with electrodes in contact with each other, and the lower group is several recharges with the electrodes physically separated from each other. Again, the performance is evident even without ionic transport of charge. This energy harvester transfers charge only via electrons.

[0284] These experiments, in which the electrodes were isolated from each other but allowed electrons and gases to transfer freely, demonstrated the use of only electrons or charged gases to transfer charge between electrodes. Ionization of oxygen occurred within a single electrode (using water vapor as a reagent) where oxygen was transferred as a gas as electrons moved from each cathode toward the anode.

[0285] The improved performance when electrodes are assembled closer to each other is a physical advantage, not an electrochemical advantage.

[0286] Without being bound by theory, it is believed that the water present in the energy harvester does not act as an electrolyte, but rather acts as a reagent in the individual electrodes.

[0287] Example 7

[0288] Fig.19 shows a 3-layer thin film energy harvester using Figure 8 The roller mill described in was prepared as described in Example 2A and Example 2B above (Run No. 36416). A gold-plated 10 mil brass liner 1 inch diameter disk (1901) was placed between each thin layer anode (7A1), separator (7A2) and cathode (7A3) between a pair of gold-plated current collectors (7B1 and 7B2).

[0289] Fig. 20 Shown in Fig.19 Figure 2 shows voltammograms of the energy harvester with separated electrodes as described in , where the curves are from an energy harvester with 3 thin roll electrodes where the electrodes were simply pressed together with no spacers. The top line has a gold plated brass spacer between the electrodes. The bottom line was constructed with no spacers at all and the electrodes pressed together. It shows a lower voltage but the current density is 10 times higher. Both energy harvesters are operational but the parameters obtained are different. The complete barrier of liquids, ions and gases clearly does not hinder the performance, proving that the energy harvester uses only electrons to transfer charge.

[0290] Fig.21Long term OCV is shown for this thin electrode energy harvester with a solid spacer between the electrodes in cell 36516 (Dec 31, 2016). The energy harvester was exposed to oxygen at the beginning, at which point the OCV reached 0.12 volts, then dropped a bit, but still maintained the voltage. At about 700 minutes, more oxygen was given, and the performance improved again. It should be noted that the environmental "chamber" was just a plastic bag with a cable tie closed at the top. This was not an airtight seal by any means. So atmospheric gases do diffuse over time. At about 825 minutes, argon was allowed to fill the bag, and a sharp drop in performance was observed. At about 875 minutes, oxygen was reintroduced into the "chamber", and the performance went back up again. These results show that the energy harvester still works whether the electrodes are clamped together or separated by an impermeable nickel layer. This suggests that one can roll or brush the active ingredient onto the metal foil to increase the surface area.

[0291] Example 8

[0292] Fig. 22 A cross section of a 3 layer energy harvester made using the Teflon roller milling method described above in Example 2B is shown. In this case, each electrode was a different diameter with the bottom layer being a 1" (25.4mm) diameter cathode (7A3), the separator was 7 / 8" (22.2mm) (7A2), and the anode was 3 / 4" (19mm) (7A1). Paper insulation was made to ensure that the current collectors would not short the anode and separator (2201) to the current collector plates (7B1 and 7B2). This ensured that there were no accidental shorts between the anode and cathode, or even a direct short of the energy harvester. The energy harvester was subjected to a variety of tests where it performed the best of all previous tests.

[0293] Short circuit test: Fig.23The current density for three 24-hour dead short tests of cell 24417 is shown (September 1, 2017). The current density is now much higher than previous tests that used thin electrodes and progressively smaller electrodes to prevent accidental shorts between the electrodes. Several conditions can be seen in these lines, such as changing gases. Consider the lowest line, which is the initial discharge. The energy harvester is dry after manufacture. Near 90% of the test, it is exposed to 100% relative humidity (RH) and its performance improves considerably. The next line above the lowest line shows the continuation of the same energy harvester in air and 100% RH until 20% of the test when pure oxygen is introduced. At about 25%, pure argon is introduced to remove all oxygen from the test chamber. At 85%, atmospheric air (20% oxygen) is introduced. The top line is after standing in air at 100% RH, and at the end of the 24-hour test, oxygen is introduced, giving a considerable increase in the current density output. The effect of the oxygen in the atmosphere is very obvious in the resulting open circuit voltages, with oxygen giving the highest values.

[0294] OCV Recovery Test: Fig.24 Shown in Fig.23 The bottom line shows the OCV recovery in argon (small amounts of oxygen). Remember that the test chamber was not completely sealed to prevent contaminating oxygen from the air. The middle line is in air, and the top line is in 100% oxygen. Again, it is clear that atmospheric gases play a large role in performance.

[0295] Fig.25 Summarized from Fig.24 The OCV between tests of the graph shown in . The light grey column shows the growth rate (ie the initial slope of the recovery) and the darker column shows the voltage reached after 30 seconds.

[0296] The energy harvester was tested primarily under 24-hour full short-circuit discharge cycles and with varying rest times. Fig.26 A full short circuit discharge is shown for the life of the energy harvester (Run No. 24417) plotted in the order of the tests. Most of the columns are the current density at the end of the 24 hour test in air at 100% RH. The two gray columns #4 and #5 were each discharged in oxygen for one hour. The fifth to last (#20) is a 12 day discharge in air at 100% RH. The fourth to last (#21) is a series with ambient gas changes. The longest discharge is shown by the last column (#24), which shows the current density after 5 days of discharge. As time goes by, it increases in current output. The energy harvester shows automatic recharging as it discharges. During this test series of 560 hours (23 days), the total discharge output of the energy harvester was 1.5 coulombs.

[0297] The final column in the test was repeatedly interrupted to obtain impedance values. Fig. 27 This long-duration discharge is shown over many days of discharge with varying atmospheric gas composition. The discharge is interrupted several times for several minutes to measure the impedance number (as shown later in Fig.29 In this long-term test, the gas test period starts with dry conditions, followed by about 24 hours of 100% RH air environment. After 12 days, the operation is described below. Fig. 27 A series of gas tests are discussed. Then at about 290 hours (12 days), the chamber was filled with argon to displace the oxygen.

[0298] Fig.28 Exemplary results are provided for the first section in the case of air, followed by oxygen at about 294.5 hours (12.25 days), at which the output increases. This is followed by replacement of the oxygen with argon at about 294 hours. Air is then introduced after 30 minutes until about 300 hours, when argon is introduced. This is followed by the application of much argon due to the constant diffusion of the atmosphere into the test chamber. Again, the importance of oxygen is shown for this energy harvester.

[0299] about Fig. 27 , the chamber was refilled with 100% RH air and the run continued for another 6 days. Not only did it fully recover, but it also gave a higher current density after the test. The cell ran for nearly 20 days with no degradation, and the current density increased during the test.

[0300] Fig.29 The 65kHz AC impedance as a function of the current density of the energy harvester is shown as the energy harvester is humidified from dry conditions to water saturated conditions. There is a semi-logarithmic relationship (where R 2 The value is 99%), which shows that it is a first order relationship. Without intending to be bound by theory, this seems to indicate that the ingress of water causes a change in impedance as the current density increases. In this example, the AC impedance decreases, which increases the current density.

[0301] Example 10

[0302] The 3-layer energy harvester was made using the Teflon roller milling method described above in Example 2B: Roller Electrode. In this example, Teflon (PTFE) was added as an aqueous suspension called Teflon 30. These particles were very small compared to the T7c powder described previously.

[0303] The recipe for this 12-gram mixture is:

[0304] Table 3

[0305] molecular <![CDATA[CeO2]]> <![CDATA[WO 2.9 ]]> <![CDATA[Ti4O7]]> <![CDATA[Co3O4]]> T30 <![CDATA[H2O]]> unit anode 2 4 6 2.76 1.5 g Partition 4 8 2.066 0.84 g cathode 2 4 6 2.421 0.33 g

[0306] In this aspect, 40 volume percent Teflon was added to each electrode, as used for Teflon 7C.

[0307] The procedure is as follows:

[0308] 1) Weigh the active powder as usual, but without Teflon 7C

[0309] 2) Place the powder in a 100cc beaker and add 50cc of distilled water

[0310] 3) Insert the stirring rod and create a deep vortex without sucking in air

[0311] 4) Add Teflon emulsion T30 drop by drop

[0312] 5) Allow stirring to continue for about 30 minutes

[0313] 6) Prepare a Buckner funnel and filter the slurry under high vacuum

[0314] 7) Place the filter paper and the filter cake still attached in a glass dish

[0315] 8) Place in drying oven at 120°C until dry (~6 hours for this 12 gram formulation).

[0316] 9) Optionally, place in a desiccator at room temperature until dry (~24 hours).

[0317] 10) After adding a small aliquot of water to the formulation, the dry cake was scraped off the paper and ground in a high shear blender.

[0318] 11) Use a roll mill to form the electrode.

[0319] The resulting electrodes are stronger than those made with dry methods and can be formed into energy harvesters fairly easily.

[0320] Fig.30 Shown are the limiting currents taken from the initial voltammograms after building several energy harvesters. The first column shows the limiting current (LC) of the new energy harvester using dry Teflon 7C adhesive before humidification. The second column shows the LC after humidification. The third column shows the initial performance of the energy harvester made using liquid emulsion T30 adhesive, with water removed via evaporation.

[0321] Without wishing to be bound by theory, Fig.31The diagram generally shows the charge flow of an exemplary energy harvester described herein. It is believed that the oxygen carries its two negative charges (electrons) into the cathode 7A3. The oxygen is embedded in the crystal structure and defects of the cathode material 3101 (e.g., Co3O4), creating excess electrons that slide onto the CeO2 crystals with their loosely bound oxygen atoms, which carry two electrons. These electrons are transported to the CeO2 crystals by the WO 2.9 The lower electronegativity of the anode 7A1 is attracted and facilitated by the CeO2 "electrolyte" 3102, freely migrating to the separator layer 7A2. The transition metal suboxide (e.g., Ti4O7) in the anode 7A1 has a greater electronegativity than the Co3O4 3101 of the cathode 7A3. These electrons are released by the oxygen that reacts with the hydroxyl ions, forming water vapor in the anode body 3103, which escapes to the environment. The current collector 7B1 accumulates the excess electrons, forming a potential across the load 3104, returning the electrons to the cathode current collector 7B2.

[0322] Layer 7A2 is optionally not included.

[0323] Embodiment 11

[0324] Low impedance three-electrode design:

[0325] In this aspect, the battery uses high impedance parts to separate the charges. For example, the anode and cathode can contain carbon (e.g., carbon black or graphite) to reduce the impedance of the electrodes while maintaining high impedance in the SSE layer as a solid separator located between the electrodes ( Fig.32 ). In another aspect, Ti4O7 is added to SSE to increase DC resistance. In this aspect, the power density can be increased by about 10 times.

[0326] exist Fig.32 In an exemplary aspect of the invention, "A" is the anode and contains the active compound plus carbon, "Sep" is the SSE, and "C" is the cathode plus carbon. In another aspect, the carbon loading can be about 5%. In another aspect, Ti4O7 or other impedance increasing components can be added to the SSE separator layer to increase its resistance. Carbon was tested in the form of carbon black using CABOT VulcanXC72R (also referred to as "V72") and optionally Asbury Graphite Mills "Nano 307" powdered graphite. Loadings below 5% are best, but even 0.5% is beneficial. Mixtures of the two carbon types were also tested.

[0327] The DC resistance of the components was measured to better understand the impedance characteristics of the exemplary battery. Table 4 shows the DC resistance of the battery components. Components 1-4 are the original chemicals, components 5-6 are carbon-free anodes and carbon-containing anodes, 7 is SSE, and 8 and 9 are carbon-free cathodes and carbon-containing cathodes. Items 5-9 also all contain 40 volume percent of unsintered Teflon powder.

[0328] Table 4 Components and Electrode Ohm-cm

[0329]

[0330] Fig.33 An exemplary three-layer design was shown to produce a discharge rate 12.5 times higher than the 34818 cell (Dec. 14, 2018), which was the highest previously tested without carbon in the electrodes. The cell is a two-electrode design.

[0331] Fig.34 Dead short circuit discharge is shown for cells with and without carbon in the electrodes at an eight (8) times increase in current density.

[0332] like Fig.35 , a constant potential discharge of the cell is shown, starting in humidified air (20% oxygen) and then in 100% humidified oxygen at 4.5 hours. At 6 hours, the gas was changed to humidified argon (0% oxygen) and back to humidified air at 12 hours. In this respect, it appears that the oxygen content affects the output. Without being bound by theory, the fact that the argon atmosphere does not reach zero suggests that the water vapor is electrolyzed to generate its own oxygen in situ.

[0333] Fig.36 Power curves for three exemplary designs are shown. The bottom curve is a two-electrode design and contains no carbon. The top two curves are three-electrode designs, one line containing 3% nanographite and the other containing 3% Vulcan 72 carbon black added to the anode and cathode, with an SSE layer between the two to separate the charge across their relatively high impedance.

[0334] Next, carbon black was used in the anode and cathode at the same loading level as graphite in the previous run. After "activation" (short circuit for 24 hours, then OCV for 6 hours), the power density of this cell containing carbon black was slightly higher than that of graphite, but graphite reached a slightly higher exchange potential. In another aspect, carbon black and graphite can be mixed in the electrodes.

[0335] In one aspect, carbon can be added to the anode and cathode at between about 2% to about 6%. In another aspect, the amount of carbon added to the anode and cathode can be about 4%.

[0336] Example 12

[0337] If the binder is liquid based (which would then be removed), these electrodes can be produced using a brush-on method. The brush-on energy harvesters were developed using a 25% dilution of latex medium (Batch 03717). Each electrode was a rolled material that was then reground to shred the fibrillated Teflon fibers. The resulting mixture was then mixed 50 / 50 with a 25% solution of latex binder to produce a thick, paint-like material. The paint-like material was brushed onto a 1 mil nickel sheet that had previously been brushed with a thin coating of a 50% diluted Timrex LB1016 graphite conductive paint. Each electrode was dried between applications. The final thickness was only 12 mils (0.012" or 0.3 mm). The discs were then blanked out using a 3 / 4" arch punch. The resulting energy harvester demonstrated feasibility, but output low current density values ​​compared to either the roll-on method or the pellet method.

[0338] Assembly Mode and Method: In one aspect, the energy harvester is assembled as follows:

[0339] a. Solid anode current collector, which should be of a material that does not react with the active ingredients. This could be nickel, gold, gold-plated metal, or carbon, and should cover most or the entire anode surface.

[0340] b. An anode comprising a mixture of a solid electrolyte and a suboxide of a transition metal. The physical form of this layer is compressed and held together using a porous binder. It can also be applied as a coating using a liquid binder which is dried after application.

[0341] c. A layer called the "separator" which consists only of a solid electrolyte and a binder. It can be the same thickness as the anode and cathode, or it can be thinner than the anode and cathode, or it can be omitted all together.

[0342] d. A cathode comprising a solid electrolyte and a suboxide of a transition metal that is less electronegative than the suboxide used in the anode.

[0343] e. Cathode current collector, which should be of a material that does not react with the active ingredients. This could be nickel, gold, gold-plated metal or carbon, and should cover most or the entire cathode surface. This layer is preferably porous, such as a perforated metal of foamed metal, porous carbon.

[0344] Binders: The powders described herein are not sintered, but rather are bound together using a binder. They are therefore "green" (unsintered). Binders that can work in this energy harvester include fibrillated Teflon (PTFE), latex, albumen, hydrogels, aerogels, or other organic or inorganic binders with low conductivity. The material needs to be porous and have a very high internal impedance; higher than the active ingredient of the invention. The binder can start with a solvent that, when dried, results in a high impedance, high porosity binder.

[0345] Additional Applications: This energy harvester can be used in low power applications where there is a constant source of atmospheric air. Preferably this air is moving, such as in a stream from a ventilation fan or on a moving vehicle. If on a digital watch, the housing of the energy harvester will need to be porous for air to enter. Examples include the following list and others:

[0346] a. Gas sensors, due to their sensitivity to atmospheric gas composition

[0347] b. Any low power device, such as electronic watch, low power LED

[0348] c. Anywhere there is continuous air movement, such as in a moving vehicle, in the flow of cooling or ventilation fans, on the blades of a windmill, on the wings of an aircraft, and many other places.

[0349] d. Brushing the anode portion onto a solid surface, on which subsequent layers are brushed, terminating at some porous current collector, which will result in a large surface area and, for many applications, high current output.

[0350] Unless otherwise indicated, the potentials reported herein (E o ) comes from the following source: en.wikipedia.org / wiki / Standard_electrode_potential_(data_page).

[0351] The term "energy harvester" as used herein is not limited to a closed body with electrodes in mechanical terms, but may be open to the environment on one or more sides of the device. The term "solid-state energy harvester" may be interpreted as a "solid-state energy source"

[0352] The device may function as an energy storage unit such as a battery or a capacitor.

[0353] The pair used in this paper Definitions of notation can be found in many sources, including Wikipedia or more academic websites such as ( https: / / www.tf.uni-kiel.de / matwis / amat / def_en / kap_2 / backbone / r2_4_2.html ).

[0354] References cited in this disclosure are hereby incorporated in their entirety.

[0355] Although the present invention has been disclosed with reference to certain embodiments, many modifications, changes and variations of the described embodiments are possible without departing from the sphere and scope of the invention as defined in the appended claims. Therefore, it is intended that the present invention is not limited to the described embodiments, but that the present invention has the full scope defined by the language of the appended claims and their equivalents.

[0356] This disclosure also relates to the following items:

[0357] 1. A solid-state energy harvester, comprising:

[0358] a first layer comprising a first transition metal suboxide and a solid state electrolyte (SSE);

[0359] a second layer comprising a mixture of a second transition metal suboxide and a lanthanide oxide or lanthanide dioxide, wherein the mixture forms a SSE;

[0360] a third layer comprising a third transition metal suboxide and SSE; and

[0361] The first transition metal suboxide and the third transition metal suboxide are different from each other.

[0362] 2. The solid-state energy harvester of item 1, wherein the first transition metal suboxide is selected from the group consisting of tungsten suboxide, cobalt suboxide, Na 1.0 Mo 1.5 WO 6.0 、Na 0.9 Mo6O 17 、Na 1.0 Ti 1.5 WO 4.5 、Na 1.2 Ti 0.34 WO4, Ti4O7, Ti5O9, K 1.28 Ti8O 16 , K 1.04 Ti8O 16 , K 0.48 Ti8O 16 、Na4WO3、Na 0.90 WO 1.81 、Na 0.82 WO 1.81 、Na0.74 WO 1.81 , K 0.9 WO3、WO 2.72 , WO 2.82 , WO 2.9 、Na2WO4、Na 8.2 WO, Na2O2WO3, Na 1.2 Ti 0.34 WO4、Na 1.2 Cu 0.31 WO 7.2 、Na 1.2 Mo 0.31 WO 5.2 and Na2O4WO3.

[0363] 3. The solid-state energy harvester of item 1, wherein the third transition metal suboxide is selected from the group consisting of tungsten suboxide, cobalt suboxide, Co3O4, Na 1.0 Mo 1.5 WO 6.0 、Na 0.9 Mo6O 17 、Na 1.0 Ti 1.5 WO 4.5 、Na 1.2 Ti 0.34 WO4, K 1.28 Ti8O 16 , K 1.04 Ti8O 16 , K 0.48 Ti8O 16 、Na4WO3、Na 0.90 WO 1.81 、Na 0.82 WO 1.81 、Na 0.74 WO 1.81 , K 0.9 WO3、WO 2.72 , WO 2.82 , WO 2.9 、Na2WO4、Na 8.2 WO, Na2O2WO3, Na 1.2 Ti 0.34 WO4、Na 1.2 Cu 0.31 WO 7.2 、Na 1.2 Mo 0.31 WO 5.2 and Na2O4WO3.

[0364] 4. The solid-state energy harvester of item 1, wherein the first transition metal suboxide, the second transition metal suboxide, or the third transition metal suboxide is selected from the group consisting of: boron, iron, copper, and nickel.

[0365] 5. The solid-state energy harvester of item 1, wherein the first transition metal suboxide is an alkali metal suboxide.

[0366] 6. The solid-state energy harvester of item 5, wherein the alkali metal suboxide is selected from the group consisting of rubidium and cesium.

[0367] 7. A solid-state energy harvester as described in item 1, wherein the lanthanide oxide or lanthanide dioxide is selected from the group consisting of: cerium dioxide, lanthanum oxide or dioxide, praseodymium oxide or dioxide, neodymium oxide or dioxide, promethium oxide or dioxide, samarium oxide or dioxide, europium oxide or dioxide, gadolinium oxide or dioxide, terbium oxide or dioxide, dysprosium oxide or dioxide, holmium oxide or dioxide, erbium oxide or dioxide, thulium oxide or dioxide, ytterbium oxide or dioxide, and lutetium oxide or dioxide.

[0368] 8. A solid-state energy harvester as described in item 1, wherein the first transition metal suboxide is Ti4O7.

[0369] 9. The solid-state energy harvester of item 1, wherein the second transition metal suboxide is WO 2.9 .

[0370] 10. A solid-state energy harvester as described in item 1, wherein the third transition metal suboxide is Co3O4.

[0371] 11. The solid-state energy harvester of item 1, wherein each of the first layer and the third layer is substantially free of precious metals.

[0372] 12. The solid-state energy harvester of item 1, wherein the first layer, the second layer, and the third layer each further comprise an adhesive.

[0373] 13. The solid-state energy harvester of item 12, wherein the binder is selected from the group consisting of: unsintered Teflon (PTFE), FEP, paraffin wax, and epoxy resin.

[0374] 14. The solid-state energy harvester of item 1, wherein the first layer is an anode and the third layer is a cathode.

[0375] 15. The solid-state energy harvester of item 14, wherein the anode comprises between about 0.01% and about 14% water.

[0376] 16. The solid-state energy harvester of item 14, wherein the cathode comprises between about 0.01% and about 4% water.

[0377] 17. The solid-state energy harvester of item 1, wherein the first transition metal suboxide, the second transition metal suboxide, and the third transition metal suboxide each have a stoichiometry M x-y ,in:

[0378] M is a transition metal,

[0379] x is the base value of the transition metal M,

[0380] y is the deviation from the population, and

[0381] When M is titanium, x is 4 and y is at least 0.5,

[0382] When M is cobalt, x is 3 and y is at least 0.3, and

[0383] When M is tungsten, x is 5 and y is at least 0.2.

[0384] 18. The solid-state energy harvester of clause 1, wherein the first layer is electrically connected to a first current collector, and wherein the third layer is electrically connected to a second current collector.

[0385] 19. The solid-state energy harvester of clause 18, wherein the first current collector and the second current collector comprise a metal selected from the group consisting of gold, nickel, copper, brass, bronze, and carbon.

[0386] 20. The solid-state energy harvester of clause 18, wherein at least one of the first current collector and the second current collector comprises a porous material.

[0387] 21. The solid-state energy harvester of clause 20, wherein the porous material comprises greater than about 50% pores.

[0388] 22. The solid-state energy harvester of clause 21, wherein the pores have a diameter from about 10 μm to about 40 μm.

[0389] 23. The solid-state energy harvester of clause 20, wherein the first current collector and the second current collector each comprise metal foam.

[0390] 24. The solid-state energy harvester of clause 20, wherein the first current collector and the second current collector each comprise a porous material.

[0391] 25. The solid-state energy harvester of clause 24, wherein the porous material comprises greater than about 50% pores.

[0392] 26. The solid-state energy harvester of clause 25, wherein the pores have a diameter from about 10 μm to about 40 μm.

[0393] 27. The solid-state energy harvester of clause 20, wherein the first current collector and the second current collector each comprise perforated metal.

[0394] 28. The solid-state energy harvester of clause 20, wherein the first current collector and the second current collector each comprise a porous conductive material.

[0395] 29. The solid-state energy harvester of clause 20, wherein the porous material is carbon.

[0396] 30. The solid-state energy harvester of clause 29, wherein the carbon comprises greater than about 50% pores.

[0397] 31. The solid-state energy harvester of clause 30, wherein the pores have a diameter from about 10 μm to about 40 μm.

[0398] 32. A solid-state energy harvester system comprising a first energy harvester and a second energy harvester, wherein the first energy harvester and the second energy harvester comprise the solid-state energy harvester of item 1, and wherein the first layer of the first energy harvester is electrically connected to the third layer of the second energy harvester.

[0399] 33. The solid-state energy harvester system of item 32, wherein the first layer of each of the first energy harvester and the second energy harvester comprises a titanium suboxide, and the third layer of each of the first energy harvester and the second energy harvester comprises a cobalt suboxide.

[0400] 34. The solid-state energy harvester system of clause 33, wherein the first layer of the first energy harvester and the third layer of the second energy harvester are each operably attached to a current collector.

[0401] 35. A solid-state energy harvester comprising:

[0402] a first layer comprising a first transition metal suboxide, a tungsten suboxide, and ceria;

[0403] a second layer comprising tungsten suboxide and ceria; and

[0404] a third layer comprising a second transition metal suboxide, a tungsten suboxide, and ceria;

[0405] wherein the first transition metal suboxide and the second transition metal suboxide are different from each other,

[0406] The first layer, the second layer and the third layer are bonded together using an adhesive,

[0407] The first layer further comprises titanium suboxide,

[0408] The third layer further comprises a cobalt suboxide; and

[0409] The solid-state energy harvester generates electrical current in the presence of oxygen and water vapor.

[0410] 36. A method of manufacturing a solid-state energy harvester, comprising:

[0411] grinding a first mixture comprising a first transition metal suboxide, a solid electrolyte comprising a lanthanide element and the first transition metal suboxide, and a binder to form a first layer;

[0412] grinding a second mixture comprising a solid electrolyte comprising a lanthanide element and a binder to form a second layer;

[0413] grinding a third mixture comprising a second transition metal suboxide, a solid electrolyte, and a binder, and forming a third layer; and

[0414] The first layer is connected to the second layer, and the second layer is connected to the third layer, wherein the first layer is an anode, the second layer is an SSE separator, and the third layer is a cathode, and the first transition metal suboxide and the second transition metal suboxide are different from each other.

[0415] 37. The method of item 36, wherein the first transition metal suboxide and the second transition metal suboxide are each selected from the group consisting of tungsten suboxide, cobalt suboxide, Co3O4, Na 1.0 Mo 1.5 WO 6.0 、Na 0.9 Mo6O 17 、Na 1.0 Ti 1.5 WO 4.5 、Na 1.2 Ti 0.34 WO4, Ti4O7, Ti5O9, K 1.28 Ti8O 16 , K 1.04 Ti8O 16 , K 0.48 Ti8O 16 、Na4WO3、Na 0.90 WO 1.81、Na 0.82 WO 1.81 、Na 0.74 WO 1.81 , K 0.9 WO3、WO 2.72 , WO 2.82 , WO 2.9 、Na2WO4、Na 8.2 WO, Na2O2WO3, Na 1.2 Ti 0.34 WO4、Na 1.2 Cu 0.31 WO 7.2 、Na 1.2 Mo 0.31 WO 5.2 and Na2O4WO3.

[0416] 38. The method of claim 36, wherein the first mixture and the second mixture are ground in a high shear, high intensity blender.

[0417] 39. The method of claim 36, wherein the first layer, the second layer, and the third layer are not separated by physical partitions.

[0418] 40. The method of item 36, wherein the first transition metal suboxide and the second transition metal suboxide are each selected from the group consisting of titanium, cobalt, tungsten, or cesium.

[0419] 41. The method of claim 36, wherein the first transition metal suboxide comprises a titanium suboxide.

[0420] 42. The method of claim 36, wherein each of the first mixture and the second mixture has a water content of less than about 25 weight percent.

[0421] 43. The method of claim 36, wherein the second transition metal suboxide comprises a cobalt suboxide.

[0422] 44. The method of item 43, wherein each of the first layer, the second layer, and the third layer has a water content of less than about 5 weight percent.

[0423] 45. The method of item 36, wherein each of the first layer, the second layer, and the third layer comprises a solid electrolyte comprising tungsten suboxide and cerium dioxide.

[0424] 46. ​​The method of claim 36, wherein each of the first mixture and the second mixture and the third mixture has a water content of less than about 10 weight percent.

[0425] 47. The method of item 36, wherein the binder is selected from the group consisting of unsintered polytetrafluoroethylene (PTFE), FEP, paraffin wax, and epoxy resin.

[0426] 48. The method of item 47, wherein the binder is less than about 50 volume percent of each of the first layer, the second layer, and the third layer.

[0427] 49. The method of item 36 further comprises compressing the first mixture, the second mixture, and the third mixture or a combination of the first mixture, the second mixture, and the third mixture in a roller mill to produce a reverse extrudate.

[0428] 50. The method of item 36, wherein the solid-state energy harvester does not include physical partitions between the first layer and the second layer and the third layer.

[0429] 51. The method of claim 36, wherein the anode comprises about 17% (w / w) CeO2, 33% (w / w) WO 2.9 , 50% (w / w) Ti4O7 and 40 volume percent of powdered PTFE.

[0430] 52. The method of claim 36, wherein the cathode comprises about 17% (w / w) CeO2, 33% (w / w) WO 2.9 , 50% (w / w) Co3O4 and 40 volume percent of powdered PTFE.

[0431] 53. The method of item 36, wherein:

[0432] The anode comprises about 17% (w / w) CeO2, 33% (w / w) WO 2.9 , a mixture of 50% (w / w) Ti4O7 and 40 volume percent of powdered PTFE;

[0433] The SSE separator comprises about 67% (w / w) WO 2.9 , 33% (w / w) CeO2 and 40 volume percent of powdered PTFE, and

[0434] The cathode comprises about 17% (w / w) CeO2, 33% (w / w) WO 2.9 , 50% (w / w) Co3O4 and 40 volume percent of powdered PTFE.

[0435] 54. A method as described in item 36, wherein each of the first layer, the second layer and the third layer contains Teflon particles, the adhesive includes a powder, and each of the first layer and the second layer is manufactured using a roller mill to force the powder through the rollers of the mill and extrude the Teflon particles into fibrils.

[0436] 55. The method of clause 36, wherein the solid-state energy harvester is enclosed in a non-conductive, substantially airtight housing.

[0437] 56. The method of item 55, wherein the non-conductive, substantially gas impermeable shell has a gas inlet and a gas outlet on opposite sides of the non-conductive, substantially gas impermeable shell.

[0438] 57. The method of clause 55, wherein the non-conductive, substantially air-impermeable housing is made of a material selected from the group consisting of polyacrylates and polycarbonates.

[0439] 58. A solid-state energy harvester comprising:

[0440] an anode comprising a first transition metal suboxide;

[0441] a separator comprising a solid state electrolyte (SSE) comprising a mixture of a second transition metal suboxide and a lanthanide oxide or a lanthanide dioxide; and

[0442] A cathode comprises a third transition metal suboxide.

[0443] 59. The solid-state energy harvester of clause 58, wherein the first transition metal suboxide, the second transition metal suboxide, and the third transition metal suboxide are different from one another.

[0444] 60. The solid-state energy harvester of clause 58, wherein the anode and the cathode further comprise carbon.

[0445] 61. The solid-state energy harvester of clause 60, wherein the carbon is selected from the group consisting of carbon black and graphite.

[0446] 62. The solid-state energy harvester of clause 58, wherein the amount of carbon in the anode is from about 2% to about 6%.

[0447] 63. The solid-state energy harvester of item 62, wherein the amount of carbon in the anode is 3%.

[0448] 64. A solid-state energy harvester as described in claim 58, wherein the separator also contains Ti4O7.

[0449] 65. A solid-state energy harvester comprising:

[0450] a first layer comprising a first transition metal suboxide and a solid state electrolyte (SSE); and

[0451] a second layer, the second layer comprising a second transition metal suboxide and SSE;

[0452] The first transition metal suboxide and the second transition metal suboxide are different from each other.

[0453] 66. The solid-state energy harvester of clause 65, wherein the first layer is separated from the second layer by a conductive metal layer.

[0454] 67. The solid-state energy harvester of item 66, wherein the conductive metal layer is an expanded metal.

[0455] 68. The solid-state energy harvester of clause 67, wherein the expanded metal is selected from the group consisting of nickel, gold, titanium, and carbon.

[0456] 69. A method of manufacturing a solid-state energy harvester, comprising:

[0457] grinding a first mixture comprising a first transition metal suboxide, a solid electrolyte comprising a lanthanide element and the first transition metal suboxide, and a binder to form a first layer;

[0458] grinding a second mixture comprising a second transition metal suboxide, a solid electrolyte, and a binder and forming a second layer; and

[0459] The first layer is connected to the second layer, wherein the first layer is an anode and the second layer is a cathode, and the first transition metal suboxide and the second transition metal suboxide are different from each other.

Claims

1. A solid-state energy harvester, comprising: a first layer, the first layer comprising a first transition metal suboxide and a solid electrolyte; a second layer comprising a mixture of a second transition metal suboxide and a lanthanide oxide, wherein the mixture forms a solid electrolyte; a third layer comprising a third transition metal suboxide and a solid electrolyte; and wherein the first transition metal suboxide and the third transition metal suboxide are different from each other, wherein the third transition metal suboxide is less electronegative than the first transition metal suboxide, and wherein the first layer is used as an anode and the third layer is used as a cathode.

2. The solid-state energy harvester of claim 1, wherein the first transition metal suboxide is selected from the group consisting of tungsten suboxide, cobalt suboxide, Na 1.0 Mo 1.5 WO 6.0 、Na 0.9 Mo6O 17 、Na 1.0 Ti 1.5 WO 4.5 、Na 1.2 Ti 0.34 WO4, Ti4O7, Ti5O9, K 1.28 Ti8O 16 , K 1.04 Ti8O 16 , K 0.48 Ti8O 16 、Na4WO3、Na 0.90 WO 1.81 、Na 0.82 WO 1.81 、Na 0.74 WO 1.81 , K 0.9 WO3, Na2WO4, Na 8.2 WO, Na2O2WO3, Na 1.2 Ti 0.34 WO4、Na 1.2 Cu 0.31 WO 7.2 、Na 1.2 Mo 0.31 WO 5.2 and Na2O4WO3.

3. The solid-state energy harvester of claim 1, wherein the third transition metal suboxide is selected from the group consisting of: tungsten suboxide, cobalt suboxide, Na 1.0 Mo 1.5 WO 6.0 、Na 0.9 Mo6O 17 、Na 1.0 Ti 1.5 WO 4.5 、Na 1.2 Ti 0.34 WO4, K 1.28 Ti8O 16 , K 1.04 Ti8O 16 , K 0.48 Ti8O 16 、Na4WO3、Na 0.90 WO 1.81 、Na 0.82 WO 1.81 、Na 0.74 WO 1.81 , K 0.9 WO3, Na2WO4, Na 8.2 WO, Na2O2WO3, Na 1.2 Ti 0.34 WO4、Na 1.2 Cu 0.31 WO 7.2 、Na 1.2 Mo 0.31 WO 5.2 and Na2O4WO3.

4. The solid-state energy harvester of claim 1, wherein the transition metal of the first transition metal suboxide, the second transition metal suboxide, or the third transition metal suboxide is selected from the group consisting of: iron, copper, and nickel.

5. The solid-state energy harvester of claim 1, wherein the first transition metal suboxide comprises an alkali metal.

6. The solid-state energy harvester of claim 5, wherein the alkali metal is selected from the group consisting of rubidium and cesium.

7. The solid-state energy harvester of claim 1, wherein the lanthanide oxide is selected from the group consisting of: ceria, lanthanum oxide, praseodymium oxide, neodymium oxide, promethium oxide, samarium oxide, europium oxide, gadolinium oxide, terbium oxide, dysprosium oxide, holmium oxide, erbium oxide, thulium oxide, ytterbium oxide, and lutetium oxide.

8. The solid-state energy harvester of claim 1, wherein the first transition metal suboxide is Ti4O7.

9. The solid-state energy harvester of claim 1, wherein the second transition metal suboxide is WO 2.9 .

10. The solid-state energy harvester of claim 1, wherein the third transition metal suboxide is Co3O4.

11. The solid-state energy harvester of claim 1 , wherein each of the first layer and the third layer is substantially free of precious metals.

12. The solid-state energy harvester of claim 1, wherein the first layer, the second layer, and the third layer each further comprise an adhesive.

13. The solid state energy harvester of claim 12, wherein the binder is selected from the group consisting of unsintered Teflon (PTFE), FEP, paraffin wax, and epoxy resin.

14. The solid state energy harvester of claim 1 wherein the anode comprises between 0.01% and 14% water.

15. The solid state energy harvester of claim 1 wherein the cathode contains between 0.01% and 4% water.

16. A solid state energy harvester as claimed in claim 14 or 15, wherein the anode comprises about 7% water and the cathode comprises about 2% water.

17. The solid-state energy harvester of claim 1, wherein the first transition metal suboxide, the second transition metal suboxide, and the third transition metal suboxide each have a stoichiometry M x-y ,in: M is a transition metal, x is the base value of the transition metal M, y is the deviation from the population, and When M is titanium, x is 4 and y is at least 0.5, When M is cobalt, x is 3 and y is at least 0.3, and When M is tungsten, x is 5 and y is at least 0.

2.

18. The solid-state energy harvester of claim 1, wherein the first layer is electrically connected to a first current collector, and wherein the third layer is electrically connected to a second current collector.

19. The solid-state energy harvester of claim 18, wherein the first current collector and the second current collector comprise a material selected from the group consisting of gold, nickel, copper, brass, bronze, and carbon.

20. The solid-state energy harvester of claim 18, wherein at least one of the first current collector and the second current collector comprises a porous material.

21. The solid state energy harvester of claim 20, wherein the porous material comprises greater than 50% pores.

22. The solid state energy harvester of claim 21, wherein the holes have a diameter of from 10 μm to 40 μm.

23. The solid-state energy harvester of claim 20, wherein the first current collector and the second current collector each comprise metal foam.

24. The solid-state energy harvester of claim 20, wherein the first current collector and the second current collector each comprise a porous material.

25. The solid state energy harvester of claim 24, wherein the porous material comprises greater than 50% pores.

26. The solid state energy harvester of claim 25, wherein the holes have a diameter of from 10 μm to 40 μm.

27. The solid-state energy harvester of claim 20, wherein the first current collector and the second current collector each comprise perforated metal.

28. The solid-state energy harvester of claim 20, wherein the first current collector and the second current collector each comprise a porous conductive material.

29. The solid state energy harvester of claim 20, wherein the porous material is carbon.

30. The solid state energy harvester of claim 29, wherein the carbon comprises greater than 50% pores.

31. The solid state energy harvester of claim 30, wherein the holes have a diameter of from 10 μm to 40 μm.

32. The solid-state energy harvester of claim 2 or 3, wherein the tungsten suboxide is WO 2.72 , WO 2.82 , WO 2.9 .

33. The solid state energy harvester of claim 3, wherein the cobalt suboxide is Co3O4.

34. A solid-state energy harvester system comprising a first energy harvester and a second energy harvester, wherein the first energy harvester and the second energy harvester comprise the solid-state energy harvester of any one of claims 1-33, and wherein the first layer of the first energy harvester is electrically connected to the third layer of the second energy harvester.

35. The solid-state energy harvester system of claim 34, wherein the first layer of each of the first energy harvester and the second energy harvester comprises a titanium suboxide and the third layer of each of the first energy harvester and the second energy harvester comprises a cobalt suboxide.

36. The solid-state energy harvester system of claim 35, wherein the first layer of the first energy harvester and the third layer of the second energy harvester are each operably attached to a current collector.

37. A solid-state energy harvester comprising: a first layer comprising a first transition metal suboxide and a solid electrolyte comprising tungsten suboxide and ceria; a second layer, the second layer comprising tungsten suboxide and ceria; and a third layer comprising a second transition metal suboxide and a solid electrolyte comprising tungsten suboxide and ceria; wherein the first transition metal suboxide and the second transition metal suboxide are different from each other, wherein the second transition metal suboxide is less electronegative than the first transition metal suboxide, and wherein the first layer is used as an anode and the third layer is used as a cathode, The first layer, the second layer and the third layer are bonded together using an adhesive, The first layer further comprises titanium suboxide, The third layer further comprises a cobalt suboxide; and The solid-state energy harvester generates electrical current in the presence of oxygen and water vapor.

38. A method of manufacturing a solid-state energy harvester, comprising: grinding a first mixture comprising a first transition metal suboxide, a solid electrolyte comprising a lanthanide element and the first transition metal suboxide, and a binder to form a first layer; grinding a second mixture comprising a solid electrolyte comprising a lanthanide element and a binder to form a second layer; grinding a third mixture comprising a second transition metal suboxide, a solid electrolyte, and a binder, and forming a third layer; as well as The first layer is connected to the second layer, and the second layer is connected to the third layer, wherein the first layer is an anode, and the second layer is a solid electrolyte separator, and the third layer is a cathode, and the first transition metal suboxide and the second transition metal suboxide are different from each other, wherein the second transition metal suboxide is less electronegative than the first transition metal suboxide.

39. The method of claim 38, wherein the first transition metal suboxide and the second transition metal suboxide are each selected from the group consisting of tungsten suboxide, cobalt suboxide, Na 1.0 Mo 1.5 WO 6.0 、Na 0.9 Mo6O 17 、Na 1.0 Ti 1.5 WO 4.5 、Na 1.2 Ti 0.34 WO4, Ti4O7, Ti5O9, K 1.28 Ti8O 16 , K 1.04 Ti8O 16 , K 0.48 Ti8O 16 、Na4WO3、Na 0.90 WO 1.81 、Na 0.82 WO 1.81 、Na 0.74 WO 1.81 , K 0.9 WO3, Na2WO4, Na 8.2 WO, Na2O2WO3, Na 1.2 Ti 0.34 WO4、Na 1.2 Cu 0.31 WO 7.2 、Na 1.2 Mo 0.31 WO 5.2 and Na2O4WO3.

40. The method of claim 39, wherein the tungsten suboxide is WO 2.72 , WO 2.82 , WO 2.9 , and / or the cobalt suboxide is Co3O4.

41. The method of claim 38, wherein the first mixture and the second mixture are milled in a high shear, high intensity blender.

42. The method of claim 38, wherein the first layer, the second layer, and the third layer are not separated by physical barriers.

43. The method of claim 38, wherein the first transition metal suboxide and the second transition metal suboxide each comprise a metal selected from the group consisting of titanium, cobalt, or tungsten.

44. The method of claim 38, wherein the first transition metal suboxide comprises a titanium suboxide.

45. The method of claim 38, wherein each of the first mixture and the second mixture has a water content of less than 25 weight percent.

46. ​​The method of claim 38, wherein the second transition metal suboxide comprises a cobalt suboxide.

47. The method of claim 46, wherein each of the first layer, the second layer, and the third layer has a water content of less than 5 weight percent.

48. The method of claim 38, wherein each of the first layer, the second layer, and the third layer comprises a solid electrolyte comprising tungsten suboxide and ceria.

49. The method of claim 38, wherein each of the first mixture and the second mixture and the third mixture has a water content of less than 10 weight percent.

50. The method of claim 38, wherein the binder is selected from the group consisting of unsintered polytetrafluoroethylene (PTFE), FEP, paraffin wax, and epoxy resin.

51. The method of claim 50, wherein the adhesive is less than 50 volume percent of each of the first layer, the second layer, and the third layer.

52. The method of claim 38, further comprising compressing the first mixture, the second mixture, or the third mixture, or any combination thereof, in a roll mill to produce a reverse extrudate.

53. The method of claim 38, wherein the solid-state energy harvester does not include physical partitions between the first layer, the second layer, and the third layer.

54. The method of claim 38, wherein the anode comprises about 17% w / w CeO2, about 33% w / w WO 2.9 , a mixture of about 50% w / w Ti4O7 and about 40 volume percent powdered PTFE.

55. The method of claim 38, wherein the cathode comprises about 17% w / w CeO2, about 33% w / w WO 2.9 , a mixture of about 50% w / w Co3O4 and about 40 volume percent powdered PTFE.

56. The method of claim 38, wherein: The anode comprises about 17% w / w CeO2, about 33% w / w WO 2.9 , a mixture of about 50% w / w Ti4O7 and about 40 volume percent powdered PTFE; The solid electrolyte separator comprises about 67% w / w WO 2.9 , a mixture of about 33% w / w CeO2 and about 40 volume percent powdered PTFE, and The cathode comprises about 17% w / w CeO2, about 33% w / w WO 2.9 , a mixture of about 50% w / w Co3O4 and about 40 volume percent powdered PTFE.

57. The method of claim 38, wherein each of the first layer, the second layer, and the third layer comprises Teflon particles, the binder comprises a powder, and each of the first layer and the second layer is manufactured using a roller mill to force the powder through the rollers of the mill and extrude the Teflon particles into fibrils.

58. The method of claim 38, wherein the solid-state energy harvester is enclosed in a non-conductive, substantially air-impermeable housing.

59. The method of claim 58, wherein the non-conductive, substantially gas impermeable housing has a gas inlet and a gas outlet on opposite sides of the non-conductive, substantially gas impermeable housing.

60. The method of claim 58, wherein the non-conductive, substantially air-impermeable housing is made of a material selected from the group consisting of polyacrylate and polycarbonate.

61. The method of claim 38, wherein the first transition metal suboxide and the second transition metal suboxide each comprise cesium.

62. A solid-state energy harvester comprising: an anode comprising a first transition metal suboxide; a separator comprising a solid electrolyte comprising a mixture of a second transition metal suboxide and a lanthanide oxide; and a cathode comprising a third transition metal suboxide, wherein the third transition metal suboxide is less electronegative than the first transition metal suboxide.

63. The solid-state energy harvester of claim 62, wherein the first transition metal suboxide, the second transition metal suboxide, and the third transition metal suboxide are different from one another.

64. The solid state energy harvester of claim 62, wherein said anode and said cathode further comprise carbon.

65. The solid state energy harvester of claim 64, wherein the carbon is selected from the group consisting of carbon black and graphite.

66. The solid state energy harvester of claim 62, wherein the amount of carbon in the anode is from 2% to 6%.

67. A solid state energy harvester as claimed in claim 66, wherein the amount of carbon in the anode is 3%.

68. The solid state energy harvester of claim 62, wherein the separator further comprises Ti4O7.

Citation Information

Patent Citations

  • Rectenna solar energy harvester

    US8115683B1

  • Dye-sensitized solar cell, dye-sensitized solar cell module, and coating liquid for forming electrolyte layer

    CN102473988A

  • Material for solid oxide fuel cell, cathode including the material, and solid oxide fuel cell including the same

    CN102738492A

  • Battery

    CN106471659A

  • Solid state electrolyte cell and method for producing same

    CN1219779A